Slurry composition for heat-resistant layer of non-aqueous secondary battery, heat-resistant layer for non-aqueous secondary battery, and non-aqueous secondary battery

JP7652071B2Active Publication Date: 2025-03-27ZEON CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021548720
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-27
Filing Date
2020-08-31
Publication Date
2025-03-27
Estimated Expiration
2040-08-31

AI Technical Summary

Benefits of technology

【0016】 本発明によれば、分散安定性および塗工性に優れ、且つ、耐熱収縮性に優れると共に残存水分量が低減された非水系二次電池用耐熱層を形成し得る非水系二次電池耐熱層用スラリー組成物を提供することができる。 また、本発明によれば、耐熱収縮性に優れると共に残存水分量が低減された非水系二次電池用耐熱層、および当該耐熱層を備える非水系二次電池を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007652071000001
    Figure 0007652071000001
  • Figure 0007652071000002
    Figure 0007652071000002
Patent Text Reader

Abstract

The purpose of the present invention is to provide a slurry composition for a heat-resistant layer of a non-aqueous secondary battery, said slurry composition having high dispersion stability and good coating properties and being capable of forming a heat-resistant layer for a non-aqueous secondary battery having high thermal shrinkage resistance and a reduced residual water content. The slurry composition according to the present invention comprises a water-soluble polymer, nonconductive organic particles and water. The water-soluble polymer comprises an amide group-containing monomer unit, an acid group-containing monomer unit, and a hydroxyl group-containing monomer unit. In the water-soluble polymer, the content of the amide group-containing monomer unit is 63-98 mass% inclusive, and the content of the acid group-containing monomer unit is 1-20 mass% inclusive. The nonconductive organic particles comprise a crosslinkable monomer unit. In the nonconductive organic particles, the content of the crosslinkable monomer unit is 20-95 mass% inclusive.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a slurry composition for a heat-resistant layer of a non-aqueous secondary battery, a heat-resistant layer for a non-aqueous secondary battery, and a non-aqueous secondary battery. [Background technology]

[0002] Non-aqueous secondary batteries such as lithium ion secondary batteries (hereinafter sometimes simply referred to as "secondary batteries") are small, lightweight, have high energy density, and can be repeatedly charged and discharged, and are used in a wide range of applications. Secondary batteries generally include battery components such as electrodes (positive and negative electrodes) and a separator that separates the positive and negative electrodes. Conventionally, battery components that include a protective layer for improving heat resistance, i.e., a heat-resistant layer, have been used as such battery components.

[0003] Here, the heat-resistant layer of the secondary battery may be formed by binding non-conductive particles with a binder. Such a heat-resistant layer is usually formed by preparing a slurry composition in which non-conductive particles and a binder are dissolved or dispersed in a dispersion medium such as water (hereinafter referred to as a "slurry composition for non-aqueous secondary battery heat-resistant layer" and may be abbreviated as a "slurry composition for heat-resistant layer"). This slurry composition for heat-resistant layer is applied to a substrate such as a separator substrate or an electrode substrate, and then dried.

[0004] In recent years, in order to achieve further improvements in the performance of secondary batteries, attempts have been made to improve the binder composition used in forming the heat-resistant layer and the slurry composition for the heat-resistant layer (see, for example, Patent Document 1). Specifically, Patent Document 1 discloses a binder composition for a porous membrane of a secondary battery, which contains a polycarboxylic acid having a predetermined property and water, and reports that the binder composition for a porous membrane of a secondary battery has high storage stability, and a porous membrane for a secondary battery produced using the binder composition is easy to apply, and a secondary battery having improved performance such as high-temperature cycle characteristics can be produced. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2015 / 129408 Summary of the Invention [Problem to be solved by the invention]

[0006] However, in recent years, there has been a demand for further improvement in the performance of secondary batteries, and the conventional binder composition has room for improvement in terms of improving the dispersion stability of the slurry composition for heat-resistant layer prepared using the binder composition and further improving the coatability of the slurry composition for heat-resistant layer. In addition, it has been desired that the heat-resistant layer obtained using the conventional binder composition and the slurry composition for heat-resistant layer further improves the heat shrinkage resistance and reduces the amount of moisture brought into the secondary battery by the heat-resistant layer (i.e., reduces the amount of moisture remaining in the heat-resistant layer).

[0007] Therefore, an object of the present invention is to provide a slurry composition for a heat-resistant layer of a non-aqueous secondary battery, which is capable of forming a heat-resistant layer for a non-aqueous secondary battery that has excellent dispersion stability and coatability, and excellent heat shrinkage resistance while also having a reduced residual moisture content. Another object of the present invention is to provide a heat-resistant layer for a non-aqueous secondary battery which has excellent heat shrinkage resistance and a reduced amount of residual moisture, and a non-aqueous secondary battery including the heat-resistant layer. [Means for solving the problem]

[0008] The present inventors have conducted extensive research in order to solve the above problems. First, the present inventors came up with the idea that a slurry composition for a heat-resistant layer, which contains a water-soluble polymer containing an amide group-containing monomer unit, an acid group-containing monomer unit, and a hydroxyl group-containing monomer unit, and in which the content ratios of the amide group-containing monomer unit and the acid group-containing monomer unit are within respective predetermined ranges, non-conductive particles, and water, has excellent dispersion stability and coatability, and that the use of the slurry composition for a heat-resistant layer makes it possible to form a heat-resistant layer having excellent heat shrinkage resistance. Based on this, the inventors conducted further research and discovered that when preparing the above-mentioned slurry composition for the heat-resistant layer, the amount of residual moisture in the heat-resistant layer can also be reduced by using non-conductive organic particles having a content ratio of crosslinkable monomer units within a specified range as the non-conductive particles, and thus completed the present invention.

[0009] That is, the present invention aims to advantageously solve the above problems, and the slurry composition for non-aqueous secondary battery heat-resistant layer of the present invention is a slurry composition for non-aqueous secondary battery heat-resistant layer containing a water-soluble polymer, non-conductive organic particles, and water, wherein the water-soluble polymer contains an amide group-containing monomer unit, an acid group-containing monomer unit, and a hydroxyl group-containing monomer unit, the content ratio of the amide group-containing monomer unit in the water-soluble polymer is 63% by mass or more and 98% by mass or less, the content ratio of the acid group-containing monomer unit in the water-soluble polymer is 1% by mass or more and 20% by mass or less, the non-conductive organic particles contain a crosslinkable monomer unit, and the content ratio of the crosslinkable monomer unit in the non-conductive organic particles is 20% by mass or more and 95% by mass or less. Thus, the slurry composition for heat-resistant layer containing a water-soluble polymer and non-conductive organic particles having a predetermined composition, and water, has excellent dispersion stability and coatability. Moreover, the slurry composition for a heat-resistant layer can satisfactorily form a heat-resistant layer that is excellent in heat shrinkage resistance and has a reduced amount of residual moisture. In the present invention, the phrase "containing a monomer unit" means that "a polymer obtained by using the monomer contains a repeating unit derived from the monomer". In the present invention, the "content ratio (mass%)" of each monomer unit (each repeating unit) contained in the polymer is 1 H-NMR and 13 It can be measured using nuclear magnetic resonance (NMR) techniques such as C-NMR.

[0010] Here, in the slurry composition for a non-aqueous secondary battery heat-resistant layer of the present invention, the content ratio of the hydroxyl group-containing monomer unit in the water-soluble polymer is preferably 1% by mass or more and 25% by mass or less. If the content ratio of the hydroxyl group-containing monomer unit in the water-soluble polymer is within the above-mentioned range, the dispersion stability and coatability of the slurry composition for a heat-resistant layer can be further improved, and the heat shrinkage resistance of the heat-resistant layer can be further increased.

[0011] In addition, in the slurry composition for a heat-resistant layer of a non-aqueous secondary battery of the present invention, the hydroxyl group-containing monomer unit is preferably a hydroxyl group-containing (meth)acrylamide monomer unit. If the hydroxyl group-containing monomer unit contained in the water-soluble polymer in the slurry composition for a heat-resistant layer is a hydroxyl group-containing (meth)acrylamide monomer unit, the amount of residual moisture in the heat-resistant layer can be further reduced and the heat shrink resistance of the heat-resistant layer can be further improved. In addition, the cycle characteristics of the secondary battery can be improved. In the present invention, "(meth)acrylic" means acrylic and / or methacrylic.

[0012] In the slurry composition for non-aqueous secondary battery heat-resistant layer of the present invention, the molar ratio of the content of the hydroxyl group-containing monomer unit to the content of the acid group-containing monomer unit in the water-soluble polymer is preferably 0.70 or more. If the molar ratio of the content of the hydroxyl group-containing monomer unit to the content of the acid group-containing monomer unit in the water-soluble polymer (hereinafter sometimes abbreviated as "hydroxyl group / acid group molar ratio") is the above lower limit or more, the dispersion stability and coatability of the slurry composition for heat-resistant layer can be further improved. In the present invention, the "hydroxyl group / acid group molar ratio" is 1 H-NMR and 13 The content ratio (mol %) of the acid group-containing monomer unit and the content ratio (mol %) of the hydroxyl group-containing monomer unit are measured using a nuclear magnetic resonance (NMR) method such as C-NMR, and the calculation can be performed from these measured values.

[0013] Here, the slurry composition for non-aqueous secondary battery heat-resistant layer of the present invention preferably further contains a particulate polymer, and the glass transition temperature of the non-conductive organic particles is 110°C or higher, and the glass transition temperature of the particulate polymer is less than 20°C. By using a slurry composition for heat-resistant layer further containing a particulate polymer having a glass transition temperature of less than 20°C, the adhesion between the heat-resistant layer and the substrate can be improved. In addition, the cycle characteristics of the secondary battery can be excellent. And, if the glass transition temperature of the non-conductive organic particles is equal to or higher than the lower limit, the heat shrink resistance of the heat-resistant layer can be further improved. In the present invention, the "glass transition temperature" of the non-conductive organic particles and the particulate polymer can be measured by the method described in the examples of this specification.

[0014] The present invention also aims to advantageously solve the above problems, and the heat-resistant layer for a non-aqueous secondary battery of the present invention is characterized in that it is formed using any of the above-mentioned slurry compositions for a heat-resistant layer for a non-aqueous secondary battery. In this way, the heat-resistant layer formed from any of the above-mentioned slurry compositions for a heat-resistant layer has excellent heat shrinkage resistance and a reduced amount of residual moisture.

[0015] The present invention has an object to advantageously solve the above problems, and the nonaqueous secondary battery of the present invention is characterized by comprising the above-mentioned heat-resistant layer for a nonaqueous secondary battery. Thus, a secondary battery comprising a battery member having the above-mentioned heat-resistant layer has sufficient safety and excellent cycle characteristics. Effect of the Invention

[0016] According to the present invention, it is possible to provide a slurry composition for a heat-resistant layer of a non-aqueous secondary battery, which is capable of forming a heat-resistant layer for a non-aqueous secondary battery that has excellent dispersion stability and coatability, and also has excellent heat shrinkage resistance and a reduced amount of residual moisture. Furthermore, according to the present invention, it is possible to provide a heat-resistant layer for a nonaqueous secondary battery which has excellent heat shrinkage resistance and a reduced amount of residual moisture, and a nonaqueous secondary battery including the heat-resistant layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, an embodiment of the present invention will be described in detail. Here, the slurry composition for a non-aqueous secondary battery heat-resistant layer of the present invention can be used to form a heat-resistant layer of a non-aqueous secondary battery such as a lithium ion secondary battery. The heat-resistant layer for a non-aqueous secondary battery of the present invention is characterized in that it is formed from the slurry composition for a non-aqueous secondary battery heat-resistant layer of the present invention. The non-aqueous secondary battery of the present invention is characterized in that it includes a heat-resistant layer for a non-aqueous secondary battery prepared using the slurry composition for a non-aqueous secondary battery heat-resistant layer of the present invention.

[0018] (Slurry composition for non-aqueous secondary battery heat-resistant layer) The slurry composition for the heat-resistant layer of the present invention contains a water-soluble polymer, non-conductive organic particles, and water as a dispersion medium, and optionally further contains a particulate polymer and other components. Here, the slurry composition for heat-resistant layer of the present invention is characterized in that the water-soluble polymer contains an amide group-containing monomer unit, an acid group-containing monomer unit and a hydroxyl group-containing monomer unit, the content of the amide group-containing monomer unit is 63% by mass or more and 98% by mass or less, and the content of the acid group-containing monomer unit is 1% by mass or more and 20% by mass or less.Furthermore, the slurry composition for heat-resistant layer of the present invention is characterized in that the non-conductive organic particles contain a crosslinkable monomer unit, and the content of the crosslinkable monomer unit is 20% by mass or more and 95% by mass or less.

[0019] The slurry composition for heat-resistant layer of the present invention contains, in water, a water-soluble polymer containing an amide group-containing monomer unit, an acid group-containing monomer unit and a hydroxyl group-containing monomer unit, and the content ratio of the amide group-containing monomer unit and the acid group-containing monomer unit is within the above-mentioned range, and non-conductive organic particles containing a crosslinkable monomer unit within the above-mentioned range, so that the slurry composition for heat-resistant layer is excellent in dispersion stability and coating property, and by using the slurry composition for heat-resistant layer, a heat-resistant layer having excellent heat shrinkage resistance and reduced residual moisture can be formed. Thus, the reason why the above-mentioned effect is obtained by using the slurry composition for heat-resistant layer in which the above-mentioned water-soluble polymer and non-conductive organic particles are dissolved or dispersed in water is not clear, but it is presumed to be as follows.

[0020] First, it is believed that the amide group-containing monomer unit contained in the water-soluble polymer in the slurry composition for the heat-resistant layer functions as a main skeleton that imparts high rigidity to the water-soluble polymer, thereby improving the heat shrinkage resistance of the obtained heat-resistant layer. In addition, the acid group-containing monomer unit contained in the water-soluble polymer in the slurry composition for the heat-resistant layer functions as an adsorption site for the non-conductive organic particles by interacting with the non-conductive organic particles through electrostatic interaction in the slurry. However, if the interaction between the acid group-containing monomer unit and the non-conductive organic particles is too strong, the non-conductive organic particles may be agglomerated by pseudo-crosslinking, and the dispersion stability of the non-conductive organic particles in the slurry may decrease. Here, since the water-soluble polymer further contains a hydroxyl group-containing monomer unit, the hydration effect of the hydroxyl group can suppress the adsorption of the acid group-containing monomer unit to the non-conductive organic particles due to excessive interaction as described above. Therefore, it is considered that the dispersion stability of the non-conductive organic particles in the slurry can be improved. Furthermore, a slurry composition having such excellent dispersion stability can be applied evenly onto a substrate without variation in the amount of coating, and the resulting heat-resistant layer does not have any defects (such as streaks, uneven coating, or repellency), and therefore the slurry composition is considered to have excellent coatability as well. Furthermore, the non-conductive organic particles contained in the slurry composition for the heat-resistant layer contain a certain proportion of crosslinkable monomer units that contribute to increasing the hardness and glass transition temperature of the non-conductive organic particles, so they function well as non-conductive particles that impart heat resistance and strength to the heat-resistant layer. Moreover, the non-conductive organic particles contained in the slurry composition for the heat-resistant layer can more easily remove moisture that adheres to the surface by heating, etc., compared to non-conductive inorganic particles such as alumina. Therefore, the slurry composition for a heat-resistant layer of the present invention has excellent dispersion stability and coatability. In addition, by using the slurry composition for a heat-resistant layer of the present invention, a heat-resistant layer having excellent heat shrinkage resistance and reduced residual moisture can be obtained.

[0021] <Water-soluble polymer> The water-soluble polymer contained in the slurry composition for the heat-resistant layer of a non-aqueous secondary battery is a component that can contribute to improving the dispersion stability and coating property of the slurry composition for the heat-resistant layer. The water-soluble polymer is also a component that can function as a binder in the heat-resistant layer formed using the slurry composition for the heat-resistant layer, and can impart adhesiveness to the heat-resistant layer formed using the slurry composition for the heat-resistant layer, and can hold the non-conductive organic particles contained in the heat-resistant layer so that they do not detach from the heat-resistant layer. In the present invention, a polymer being "water-soluble" means that when 0.5 g of the polymer is dissolved in 100 g of water at 25°C, the insoluble content is less than 1.0 mass %.

[0022] Here, the water-soluble polymer contains amide group-containing monomer units and acid group-containing monomer units in respective proportions within a predetermined range, and further contains hydroxyl group-containing monomer units. The water-soluble polymer may contain repeating units other than the amide group-containing monomer units, acid group-containing monomer units, and hydroxyl group-containing monomer units (hereinafter referred to as "other repeating units").

[0023] <<Amide group-containing monomer unit>> Examples of amide group-containing monomers capable of forming amide group-containing monomer units include N-vinylacetamide, (meth)acrylamide, dimethyl(meth)acrylamide, diethyl(meth)acrylamide, N-methoxymethyl(meth)acrylamide, and dimethylaminopropyl(meth)acrylamide. Among these, acrylamide and methacrylamide are preferred, and acrylamide is more preferred, from the viewpoint of further enhancing the heat shrinkage resistance of the heat-resistant layer. The amide group-containing monomers may be used alone or in combination of two or more. In the present invention, a monomer unit having both an amide group and a hydroxyl group is included in the "hydroxyl group-containing monomer unit" but is not included in the "amide group-containing monomer unit." In the present invention, a monomer unit having both an amide group and an acid group (such as a carboxylic acid group, a sulfonic acid group, or a phosphoric acid group) is included in the "acid group-containing monomer unit" but is not included in the "amide group-containing monomer unit."

[0024] The water-soluble polymer used in the present invention must have an amide group-containing monomer unit content of 63% by mass or more and 98% by mass or less, when the amount of all repeating units (all monomer units) in the water-soluble polymer is taken as 100% by mass. The amide group-containing monomer unit content in the water-soluble polymer is preferably 65% ​​by mass or more, more preferably 67% by mass or more, even more preferably 71% by mass or more, preferably 95% by mass or less, and more preferably 90% by mass or less. If the amide group-containing monomer unit content in the water-soluble polymer is less than 63% by mass, the rigidity of the water-soluble polymer decreases, so that the heat shrink resistance of the heat-resistant layer cannot be sufficiently ensured. On the other hand, if the amide group-containing monomer unit content in the water-soluble polymer is more than 98% by mass, the dispersion stability of the slurry composition for the heat-resistant layer decreases.

[0025] <<Acid group-containing monomer unit>> Examples of the acid group-containing monomer capable of forming the acid group-containing monomer unit include a carboxylic acid group-containing monomer, a sulfonic acid group-containing monomer, a phosphoric acid group-containing monomer, etc. The acid group contained in the acid group-containing monomer unit may form a salt with an alkali metal, ammonia, etc.

[0026] Examples of the carboxylic acid group-containing monomer capable of forming the carboxylic acid group-containing monomer unit include monocarboxylic acids and derivatives thereof, dicarboxylic acids and acid anhydrides thereof, and derivatives thereof. Examples of the monocarboxylic acid include acrylic acid, methacrylic acid, and crotonic acid. Examples of the monocarboxylic acid derivatives include 2-ethylacrylic acid, isocrotonic acid, α-acetoxyacrylic acid, β-trans-aryloxyacrylic acid, and α-chloro-β-E-methoxyacrylic acid. The dicarboxylic acids include maleic acid, fumaric acid, and itaconic acid. Examples of dicarboxylic acid derivatives include methylmaleic acid, dimethylmaleic acid, phenylmaleic acid, chloromaleic acid, dichloromaleic acid, fluoromaleic acid, and maleic acid monoesters such as nonyl maleate, decyl maleate, dodecyl maleate, octadecyl maleate, and fluoroalkyl maleate. Examples of the acid anhydrides of dicarboxylic acids include maleic anhydride, acrylic anhydride, methylmaleic anhydride, and dimethylmaleic anhydride. Furthermore, as the carboxylic acid group-containing monomer, an acid anhydride which generates a carboxylic acid group upon hydrolysis can also be used.

[0027] In addition, examples of sulfonic acid group-containing monomers that can form sulfonic acid group-containing monomer units include vinyl sulfonic acid, methyl vinyl sulfonic acid, (meth)allyl sulfonic acid, styrene sulfonic acid, (meth)acrylic acid-2-ethyl sulfonate, 2-acrylamido-2-methylpropanesulfonic acid, and 3-allyloxy-2-hydroxypropanesulfonic acid. In the present invention, "(meth)allyl" means allyl and / or methallyl.

[0028] Furthermore, examples of phosphate group-containing monomers capable of forming phosphate group-containing monomer units include 2-(meth)acryloyloxyethyl phosphate, methyl-2-(meth)acryloyloxyethyl phosphate, and ethyl-(meth)acryloyloxyethyl phosphate. In the present invention, "(meth)acryloyl" means acryloyl and / or methacryloyl.

[0029] Here, the above-mentioned acid group-containing monomer may be used alone or in combination of two or more.The acid group-containing monomer that can form the acid group-containing monomer unit is preferably a carboxylic acid group-containing monomer, more preferably a monocarboxylic acid, and even more preferably an acrylic acid, from the viewpoint of improving the adhesion between the heat-resistant layer and the substrate and further improving the coating property of the slurry composition for the heat-resistant layer.

[0030] The water-soluble polymer used in the present invention must have an acid group-containing monomer unit content of 1% by mass or more and 20% by mass or less, preferably 2% by mass or more, more preferably 3% by mass or more, even more preferably 5% by mass or more, particularly preferably 7% by mass or more, preferably 16% by mass or less, and more preferably 12% by mass or less, when the amount of all repeating units (all monomer units) in the water-soluble polymer is taken as 100% by mass. If the acid group-containing monomer unit content in the water-soluble polymer is less than 1% by mass, the coating property of the slurry composition for the heat-resistant layer is reduced. In addition, the adsorption force of the water-soluble polymer to the non-conductive organic particles is reduced, so that the adhesion between the heat-resistant layer and the substrate cannot be sufficiently ensured. On the other hand, if the acid group-containing monomer unit content in the water-soluble polymer is more than 20% by mass, the dispersion stability of the slurry composition for the heat-resistant layer is reduced.

[0031] <<Hydroxyl group-containing monomer unit>> Examples of hydroxyl group-containing monomers capable of forming hydroxyl group-containing monomer units include hydroxyl group-containing (meth)acrylamide monomers such as N-hydroxymethylacrylamide, N-hydroxyethylacrylamide, N-hydroxypropylacrylamide, N-hydroxymethylmethacrylamide, N-hydroxyethylmethacrylamide, and N-hydroxypropylmethacrylamide; and hydroxyl group-containing (meth)acrylate monomers such as 2-hydroxymethylacrylate, 2-hydroxyethylacrylate, 2-hydroxypropylacrylate, 2-hydroxybutylacrylate, 2-hydroxymethylmethacrylate, 2-hydroxyethylmethacrylate, 2-hydroxypropylmethacrylate, and 2-hydroxybutylmethacrylate. Among these, from the viewpoints of further reducing the amount of residual moisture in the heat-resistant layer, further enhancing the heat shrinkage resistance of the heat-resistant layer, and improving the cycle characteristics of the secondary battery, hydroxyl group-containing (meth)acrylamide monomers are preferred, and N-hydroxyethylacrylamide and N-hydroxymethylacrylamide are more preferred. The hydroxyl group-containing monomers may be used alone or in combination of two or more. In the present invention, the term "(meth)acrylate" means acrylate and / or methacrylate.

[0032] Here, the water-soluble polymer contained in the slurry composition for the heat-resistant layer of the present invention must contain a hydroxyl group-containing monomer unit. If the water-soluble polymer does not contain a hydroxyl group-containing monomer unit, the dispersion stability and coatability of the slurry composition for the heat-resistant layer will be reduced. The content of the hydroxyl group-containing monomer unit in the water-soluble polymer is preferably 1% by mass or more, more preferably 3% by mass or more, even more preferably 4% by mass or more, preferably 25% by mass or less, more preferably 21% by mass or less, even more preferably 18% by mass or less, and particularly preferably 17% by mass or less, when the amount of all repeating units (all monomer units) in the water-soluble polymer is taken as 100% by mass. If the content of the hydroxyl group-containing monomer unit in the water-soluble polymer is 1% by mass or more, the dispersion stability and coatability of the slurry composition for the heat-resistant layer can be further improved. On the other hand, if the content of the hydroxyl group-containing monomer unit in the water-soluble polymer is 25% by mass or less, the heat shrink resistance of the heat-resistant layer can be further improved.

[0033] <<Other repeating units>> The other repeating units contained in the water-soluble polymer are not particularly limited. For example, the other repeating units include monomer units derived from known monomers, such as crosslinkable monomer units and (meth)acrylic acid ester monomer units, which will be described later in the section "Non-conductive organic particles". The water-soluble polymer may contain one type of other repeating units, or may contain two or more types. When all repeating units (all monomer units) contained in the water-soluble polymer are taken as 100% by mass, the content of other repeating units is preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 1% by mass or less, and particularly preferably 0% by mass.

[0034] <<Properties>> [Hydroxyl group / acid group molar ratio] Here, the molar ratio of the content of the hydroxyl group-containing monomer unit to the content of the acid group-containing monomer unit in the water-soluble polymer (hydroxyl group / acid group molar ratio) is preferably 0.70 or more, more preferably 0.80 or more, and even more preferably 0.90 or more. If the hydroxyl group / acid group molar ratio is 0.70 or more, the dispersion stability and coatability of the slurry composition for heat-resistant layer can be further improved. In addition, the upper limit of the hydroxyl group / acid group molar ratio is not particularly limited, but can be, for example, 5.00 or less, and can be 3.00 or less.

[0035] [Weight average molecular weight] Here, the water-soluble polymer used in the present invention preferably has a weight average molecular weight of 200,000 or more, more preferably 300,000 or more, even more preferably 400,000 or more, and preferably 2,000,000 or less, more preferably 1,500,000 or less, and even more preferably 1,000,000 or less. If the weight average molecular weight of the water-soluble polymer is 200,000 or more, the rigidity of the water-soluble polymer is improved, so that the heat shrink resistance of the heat-resistant layer can be further improved. On the other hand, if the weight average molecular weight of the water-soluble polymer is 2,000,000 or less, the viscosity of the slurry composition for the heat-resistant layer is reduced, so that the coatability of the slurry composition for the heat-resistant layer can be further improved. In the present invention, the weight average molecular weight of the water-soluble polymer can be measured by gel permeation chromatography (GPC). The weight average molecular weight of the water-soluble polymer can be adjusted, for example, by changing the type and amount of the polymerization initiator and / or polymerization promoter used in the preparation of the water-soluble polymer.

[0036] In addition, the water-soluble polymer contained in the slurry composition for heat-resistant layer of the present invention can moderately interact with the non-conductive organic particles, so that the ratio of the water-soluble polymer adsorbed to the non-conductive organic particles in the slurry composition for heat-resistant layer can be well controlled. By well controlling the ratio of the water-soluble polymer adsorbed to the non-conductive organic particles, the dispersion stability and coatability of the slurry composition for heat-resistant layer, and the adhesion between the heat-resistant layer and the substrate are sufficiently improved. In addition, from the viewpoint of further improving the dispersion stability and coatability of the slurry composition for heat-resistant layer and increasing the adhesion between the heat-resistant layer and the substrate, the ratio of the water-soluble polymer adsorbed to the non-conductive organic particles is preferably 10% by mass or more and 60% by mass or less, when the total water-soluble polymer in the slurry composition for heat-resistant layer is 100% by mass. Methods for measuring the proportion of the water-soluble polymer adsorbed to the non-conductive organic particles include, for example, a method in which the slurry composition for the heat-resistant layer is centrifuged, the non-conductive organic particles to which the water-soluble polymer is adsorbed are precipitated, and the weight loss behavior of the precipitate when heated is analyzed using Tg / DTA to calculate the proportion; and a method in which the slurry composition for the heat-resistant layer is centrifuged, and the concentration of the water-soluble polymer in the supernatant is quantified to calculate the proportion.

[0037] <<Method for preparing water-soluble polymers>> The water-soluble polymer described above is not particularly limited, and can be prepared by any method such as solution polymerization, suspension polymerization, bulk polymerization, and emulsion polymerization. In addition, as the polymerization method, addition polymerization such as ionic polymerization, radical polymerization, and living radical polymerization can be used. In addition, the polymerization initiator, polymerization promoter, emulsifier, dispersant, chain transfer agent, etc. used during polymerization can be generally used, and the amount of each agent used is generally used. Among them, the aqueous solution polymerization method using water as the polymerization solvent is preferred because it does not require a solvent removal operation, the solvent is highly safe, and there is no problem of surfactant contamination.

[0038] In addition, when water is used as a polymerization solvent and the above-mentioned monomer composition is polymerized in water to prepare an aqueous solution containing a water-soluble polymer, it is preferable to adjust the pH of the aqueous solution after polymerization to 7 or more and 9 or less. This is because, by neutralizing the obtained aqueous solution and adjusting the pH to the above range, it becomes easier to improve the viscosity stability of the slurry composition for the heat-resistant layer.

[0039] Here, the polymerization initiator that can be used for preparing the water-soluble polymer is not particularly limited, and includes known polymerization initiators such as sodium persulfate, ammonium persulfate, and potassium persulfate. Among them, it is preferable to use ammonium persulfate. The polymerization initiator may be used alone or in combination of two or more kinds at any ratio.

[0040] The polymerization promoter is not particularly limited, and known reducing polymerization promoters such as L-ascorbic acid, sodium hydrogen sulfite, and tetramethylethylenediamine can be used. Among them, it is preferable to use L-ascorbic acid. The polymerization promoter may be used alone or in combination of two or more kinds at any ratio.

[0041] <<Content>> Here, the content of the above-mentioned predetermined water-soluble polymer in the slurry composition for heat-resistant layer is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, in terms of solid content, per 100 parts by mass of non-conductive organic particles, from the viewpoint of further improving the heat shrink resistance of the heat-resistant layer. Also, the content of the water-soluble polymer in the slurry composition for heat-resistant layer is preferably 20 parts by mass or less, more preferably 12 parts by mass or less, in terms of solid content, per 100 parts by mass of non-conductive organic particles, from the viewpoint of improving the cycle characteristics of the secondary battery.

[0042] <Non-conductive organic particles> The non-conductive organic particles contained in the slurry composition for heat-resistant layer of the present invention are particles used as non-conductive particles that can improve the heat resistance and strength of the heat-resistant layer, and are usually made of a polymer that does not have binding ability. And, by using non-conductive organic particles as non-conductive particles, as described above, the amount of residual moisture in the heat-resistant layer can be reduced compared to the case of using non-conductive inorganic particles such as alumina. Furthermore, by using non-conductive organic particles as non-conductive particles, it is possible to reduce the metal wear that may occur when using non-conductive inorganic particles, and suppress metal contamination. The non-conductive organic particles are water-insoluble particles formed from a specific polymer. In the present invention, the particles being "water-insoluble" means that when 0.5 g of the polymer is dissolved in 100 g of water at 25° C., the insoluble content is 90 mass % or more.

[0043] Here, the non-conductive organic particles contain crosslinkable monomer units in a predetermined range of ratios, and may also contain monomer units other than the crosslinkable monomer units. Such monomer units other than the crosslinkable monomer units are not particularly limited, but include (meth)acrylic acid ester monomer units and hydrophilic group-containing monomer units, as well as monomer units (other monomer units) other than the crosslinkable monomer units, (meth)acrylic acid ester monomer units, and hydrophilic group-containing monomer units. Note that the non-conductive organic particles may be used alone or in combination of two or more types at any ratio.

[0044] <<Cross-linking monomer unit>> The crosslinkable monomer that can form the crosslinkable monomer unit is a monomer having two or more polymerizable double bonds (e.g., olefinic double bonds) per molecule.Here, examples of the crosslinkable monomer include polyfunctional (meth)acrylates such as allyl (meth)acrylate, ethylene di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, and trimethylolpropane-tri(meth)acrylate; polyfunctional allyl / vinyl ethers such as dipropylene glycol diallyl ether, polyglycol diallyl ether, triethylene glycol divinyl ether, hydroquinone diallyl ether, and tetraallyloxyethane; divinylbenzene; vinyl glycidyl ether; allyl glycidyl ether; methylol acrylamide; and acrylamide. Among these, from the viewpoint of further improving the heat shrinkage resistance of the heat-resistant layer, polyfunctional (meth)acrylates are preferred, and ethylene glycol dimethacrylate is more preferred. The above-mentioned crosslinkable monomers may be used alone or in combination of two or more.

[0045] Here, the non-conductive organic particles used in the present invention must have a crosslinkable monomer unit content of 20% by mass or more and 95% by mass or less, when the amount of all repeating units (all monomer units) in the non-conductive organic particles is taken as 100% by mass. The content of the crosslinkable monomer unit in the non-conductive organic particles is preferably 25% by mass or more, more preferably 30% by mass or more, even more preferably 50% by mass or more, particularly preferably 60% by mass or more, preferably 90% by mass or less, and more preferably 85% by mass or less. If the content of the crosslinkable monomer unit in the non-conductive organic particles is less than 20% by mass, the hardness of the non-conductive organic particles decreases, so that the dispersion stability of the slurry composition for the heat-resistant layer and the heat shrink resistance of the heat-resistant layer cannot be made sufficient. On the other hand, if the content of the crosslinkable monomer unit in the non-conductive organic particles is more than 95% by mass, the polymerization stability of the non-conductive organic particles cannot be sufficiently ensured, and the dispersion stability of the slurry composition for the heat-resistant layer decreases.

[0046] <<(Meth)acrylic acid ester monomer unit>> Examples of (meth)acrylic acid ester monomers that can form (meth)acrylic acid ester monomer units include acrylic acid alkyl esters such as methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, t-butyl acrylate, pentyl acrylate, hexyl acrylate, heptyl acrylate, octyl acrylate, and 2-ethylhexyl acrylate; and methacrylic acid alkyl esters such as methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, isopropyl methacrylate, n-butyl methacrylate, t-butyl methacrylate, pentyl methacrylate, hexyl methacrylate, heptyl methacrylate, octyl methacrylate, and 2-ethylhexyl methacrylate. These may be used alone or in combination of two or more. Among these, n-butyl acrylate is preferred as the (meth)acrylic acid ester monomer. In addition, the content of the (meth)acrylic acid ester monomer unit in the non-conductive organic particles is preferably 1% by mass or more, more preferably 5% by mass or more, even more preferably 10% by mass or more, and preferably 75% by mass or less, more preferably 50% by mass or less, and even more preferably 30% by mass or less, when the amount of all repeating units (all monomer units) in the non-conductive organic particles is taken as 100% by mass. If the content of the (meth)acrylic acid ester monomer unit in the non-conductive organic particles is 1% by mass or more, the polymerization stability of the non-conductive organic particles can be sufficiently ensured. On the other hand, if the content of the (meth)acrylic acid ester monomer unit in the non-conductive organic particles is 75% by mass or less, the hardness of the non-conductive organic particles is improved, so that the dispersion stability of the slurry composition for the heat-resistant layer and the heat shrink resistance of the heat-resistant layer can be further improved.

[0047] <<Hydrophilic group-containing monomer unit>> Examples of the hydrophilic group-containing monomer capable of forming the hydrophilic group-containing monomer unit include the "acid group-containing monomer" and "hydroxyl group-containing monomer" described in the "water-soluble polymer" section. These may be used alone or in combination of two or more. Among these, it is preferable to use acrylic acid as the hydrophilic group-containing monomer. The content ratio of the hydrophilic group-containing monomer unit in the non-conductive organic particles is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1% by mass or more, preferably 5% by mass or less, and more preferably 3% by mass or less, when the amount of all repeating units (all monomer units) in the non-conductive organic particles is taken as 100% by mass. If the content ratio of the hydrophilic group-containing monomer unit in the non-conductive organic particles is 0.1% by mass or more, the polymerization stability of the non-conductive organic particles can be sufficiently ensured. On the other hand, if the content ratio of the hydrophilic group-containing monomer unit in the non-conductive organic particles is 5% by mass or less, the hardness of the non-conductive organic particles is improved, so that the dispersion stability of the slurry composition for the heat-resistant layer and the heat shrink resistance of the heat-resistant layer can be further improved.

[0048] <<Other monomer units>> The other monomers capable of forming the other monomer units are not particularly limited as long as they are monomers other than the above-mentioned crosslinkable monomers, (meth)acrylic acid ester monomers, and hydrophilic group-containing monomers. Specifically, the other monomers include α,β-unsaturated nitrile monomers such as acrylonitrile and methacrylonitrile; styrene-based monomers such as styrene, chlorostyrene, vinyltoluene, t-butylstyrene, methyl vinylbenzoate, vinylnaphthalene, chloromethylstyrene, and α-methylstyrene. These may be used alone or in combination of two or more. The content ratio of other monomer units in the non-conductive organic particles is preferably 5% by mass or less, more preferably 1% by mass or less, and even more preferably 0% by mass, when the amount of all repeating units (all monomer units) in the non-conductive organic particles is 100% by mass.

[0049] <<Properties>> [Glass transition temperature] Here, the glass transition temperature of the non-conductive organic particles is preferably 110°C or higher, more preferably 150°C or higher, and even more preferably 200°C or higher. If the glass transition temperature of the non-conductive organic particles is 110°C or higher, the dispersion stability of the slurry composition for the heat-resistant layer can be further improved, and the heat shrink resistance of the heat-resistant layer can be further increased. In addition, the cycle characteristics of the secondary battery can be improved. In addition, the upper limit of the glass transition temperature of the non-conductive organic particles is not particularly limited, but can be, for example, 400°C or lower, and can be 300°C or lower. The glass transition temperature of the non-conductive organic particles can be adjusted, for example, by changing the type and amount of the monomer, polymerization initiator and / or polymerization accelerator used in the preparation of the non-conductive organic particles.

[0050] [Volume average particle size] The volume average particle diameter of the non-conductive organic particles is preferably 0.05 μm or more, more preferably 0.08 μm or more, even more preferably 0.1 μm or more, and preferably 0.5 μm or less, more preferably 0.4 μm or less. If the volume average particle diameter of the non-conductive organic particles is 0.05 μm or more, the amount of residual moisture in the heat-resistant layer can be further reduced and the cycle characteristics of the secondary battery can be improved. On the other hand, if the volume average particle diameter of the non-conductive organic particles is 0.5 μm or less, the heat-resistant layer can be densified and the heat shrink resistance of the heat-resistant layer can be further improved. In the present invention, the term "volume average particle size" means "the particle size (D50) at which the cumulative volume calculated from the small diameter side in the particle size distribution (volume basis) measured by a laser diffraction method becomes 50%." The volume average particle diameter of the non-conductive organic particles can be adjusted, for example, by changing the type and amount of the monomer, polymerization initiator and / or polymerization accelerator used in preparing the non-conductive organic particles.

[0051] <<Preparation method of non-conductive organic particles>> Here, the method for preparing the non-conductive organic particles is not particularly limited, and any method such as solution polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc. may be used. In addition, as the polymerization reaction, addition polymerization such as ionic polymerization, radical polymerization, and living radical polymerization may be used. In the polymerization, seed polymerization may be performed by employing seed particles. In addition, the polymerization solvent, emulsifier, dispersant, polymerization initiator, chain transfer agent, etc. that can be used in the polymerization may be general ones, and the amount of each of them may be the amount generally used. The polymerization initiator that can be used in the preparation of the non-conductive organic particles is not particularly limited, and includes known polymerization initiators such as sodium persulfate, ammonium persulfate, potassium persulfate, and t-butylperoxy-2-ethylhexanoate. Among them, it is preferable to use t-butylperoxy-2-ethylhexanoate. The polymerization initiator may be used alone or in combination of two or more kinds at any ratio.

[0052] <Particulate polymer> The particulate polymer that may be optionally contained in the slurry composition for heat-resistant layer of the present invention is a component that functions as a binder, similar to the above-mentioned water-soluble polymer, and is usually composed of a polymer having binding ability. By containing the particulate polymer in the slurry composition for heat-resistant layer, the adhesion between the obtained heat-resistant layer and the substrate can be improved. The particulate polymer is a water-insoluble particle formed from a specific polymer.

[0053] Here, the particulate polymer is not particularly limited as long as it is a particulate polymer that is water-insoluble and dispersible in a dispersion medium such as water, but for example, a conjugated diene polymer, a fluorine-based polymer, or an acrylic polymer can be used. Among these, it is preferable to use an acrylic polymer. If an acrylic polymer is used as the particulate polymer contained in the slurry composition for the heat-resistant layer, the adhesion between the heat-resistant layer and the substrate can be improved, and the oxidation resistance of the battery member having the heat-resistant layer can be increased. Note that the particulate polymer may be used alone or in combination of two or more types at any ratio.

[0054] <<Conjugated diene polymer>> The conjugated diene polymer is a polymer containing a conjugated diene monomer unit. Specific examples of the conjugated diene polymer include, but are not limited to, copolymers containing aromatic vinyl monomer units and aliphatic conjugated diene monomer units, such as styrene-butadiene copolymer (SBR), butadiene rubber (BR), isoprene rubber, acrylic rubber (NBR) (copolymers containing acrylonitrile units and butadiene units), and hydrogenated products thereof.

[0055] <<Fluorine-based polymer>> Specific examples of the fluorine-based polymer include, but are not limited to, polyvinylidene fluoride (PVdF) and polyvinylidene fluoride-hexafluoropropylene (PVdF-HFP) copolymer.

[0056] <<Acrylic polymer>> The acrylic polymer is a polymer containing a (meth)acrylic acid ester monomer unit. The acrylic polymer may also contain a repeating unit other than the (meth)acrylic acid ester monomer unit. Such a repeating unit is not particularly limited, and preferably includes a hydrophilic group-containing monomer unit and a crosslinkable monomer unit, but also includes a monomer unit (other monomer unit) other than the (meth)acrylic acid ester monomer unit, the hydrophilic group-containing monomer unit, and the crosslinkable monomer unit.

[0057] [(Meth)acrylic acid ester monomer unit] Examples of (meth)acrylic acid ester monomers capable of forming the (meth)acrylic acid ester monomer unit include those described in the section on "non-conductive organic particles." These may be used alone or in combination of two or more. Among these, n-butyl acrylate and 2-ethylhexyl acrylate are preferred as the (meth)acrylic acid ester monomer. In addition, the content ratio of the (meth)acrylic acid ester monomer unit in the particulate polymer is preferably more than 50 mass%, more preferably 60 mass% or more, and is preferably 99 mass% or less, and more preferably 97 mass% or less, when the amount of all repeating units (all monomer units) in the particulate polymer is 100 mass%.

[0058] [Hydrophilic group-containing monomer unit] Examples of the hydrophilic group-containing monomer that can form the hydrophilic group-containing monomer unit include those described in the section "Non-conductive organic particles". These may be used alone or in combination of two or more. Among these, it is preferable to use methacrylic acid as the hydrophilic group-containing monomer. The content ratio of the hydrophilic group-containing monomer unit in the particulate polymer is preferably 1% by mass or more and 5% by mass or less, when the amount of all repeating units (all monomer units) in the particulate polymer is 100% by mass.

[0059] [Cross-linking monomer unit] Examples of crosslinkable monomers capable of forming crosslinkable monomer units include those described in the section "Non-conductive organic particles." These may be used alone or in combination of two or more. Among these, it is preferable to use allyl glycidyl ether or polyfunctional (meth)acrylate as the crosslinkable monomer, and it is more preferable to use allyl glycidyl ether or allyl methacrylate. The content ratio of the crosslinkable monomer unit in the particulate polymer is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, and more preferably 10% by mass or less, and more preferably 5% by mass or less, when the amount of all repeating units (all monomer units) in the particulate polymer is taken as 100% by mass. If the content ratio of the crosslinkable monomer unit in the particulate polymer is 0.001% by mass or more, the particulate polymer can be prevented from excessively swelling in the electrolyte solution, thereby improving the cycle characteristics of the secondary battery, and if it is 10% by mass or less, the binding ability of the particulate polymer can be sufficiently ensured.

[0060] [Other monomer units] The other monomers capable of forming the other monomer units are not particularly limited as long as they are monomers other than the above-mentioned (meth)acrylic acid ester monomers, hydrophilic group-containing monomers, and crosslinkable monomers. Specifically, the other monomers include those described in the section on "non-conductive organic particles." These may be used alone or in combination of two or more. Among these, it is preferable to use acrylonitrile and styrene as the other monomers. The content ratio of other monomer units in the particulate polymer is preferably 1% by mass or more, preferably 35% by mass or less, and more preferably 5% by mass or less, when the amount of all repeating units (all monomer units) in the particulate polymer is 100% by mass.

[0061] <<Properties>> [Glass transition temperature] Here, the glass transition temperature of the particulate polymer is preferably less than 20° C., more preferably less than 15° C. If the glass transition temperature of the particulate polymer is less than 20° C., the adhesion between the heat-resistant layer and the substrate can be improved. In addition, the lower limit of the glass transition temperature of the particulate polymer is not particularly limited, but can be, for example, more than −120° C. or more than −60° C. The glass transition temperature of the particulate polymer can be adjusted, for example, by changing the type and amount of the monomer, polymerization initiator and / or polymerization accelerator used in the preparation of the particulate polymer.

[0062] [Volume average particle size] The volume average particle diameter of the particulate polymer is preferably 0.05 μm or more, more preferably 0.1 μm or more, and preferably 1 μm or less, more preferably 0.5 μm or less. If the volume average particle diameter of the particulate polymer is 0.05 μm or more, the cycle characteristics of the secondary battery can be improved. On the other hand, if the volume average particle diameter of the particulate polymer is 1 μm or less, the adhesion between the heat-resistant layer and the substrate can be improved. The volume average particle size of the particulate polymer can be adjusted, for example, by changing the type and amount of the monomer, polymerization initiator and / or polymerization accelerator used in the preparation of the particulate polymer.

[0063] <<Method for preparing particulate polymer>> Here, the polymerization method of the particulate polymer is not particularly limited, and any method such as solution polymerization, suspension polymerization, bulk polymerization, emulsion polymerization, etc. may be used. In addition, as the polymerization reaction, addition polymerization such as ionic polymerization, radical polymerization, living radical polymerization, etc. may be used. In addition, the polymerization solvent, emulsifier, dispersant, polymerization initiator, chain transfer agent, etc. that can be used in the polymerization can be general ones, and the amount of each of them can be the amount generally used.

[0064] <<Content>> In addition, the content of the particulate polymer in the slurry composition for heat-resistant layer is preferably 1 part by mass or more, more preferably 1.2 parts by mass or more, and even more preferably 1.4 parts by mass or more, per 100 parts by mass of non-conductive organic particles, in terms of solid content, from the viewpoint of improving the adhesion between the heat-resistant layer and the substrate. In addition, the content of the particulate polymer in the slurry composition for heat-resistant layer is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, and even more preferably 10 parts by mass or less, per 100 parts by mass of non-conductive organic particles, in terms of solid content, from the viewpoint of improving the cycle characteristics of the secondary battery.

[0065] <Dispersion medium> The dispersion medium of the slurry composition for heat-resistant layer of the present invention is not particularly limited as long as it contains water. For example, the slurry composition for heat-resistant layer of the present invention may contain only water as the dispersion medium, or the dispersion medium may be a mixture of water and an organic solvent (e.g., esters, ketones, alcohols). The slurry composition for heat-resistant layer of the present invention may contain one kind of organic solvent, or may contain two or more kinds of organic solvents.

[0066] <Other ingredients> The slurry composition for heat-resistant layer of the present invention may contain, in addition to the above-mentioned components, a reinforcing material, a leveling agent, a wetting agent, non-conductive inorganic particles, a dispersant, a viscosity modifier, an electrolyte additive, a preservative, a mildewproofing agent, an antifoaming agent, a polymerization inhibitor, and a binder other than the water-soluble polymer and particulate polymer of the present invention. These are not particularly limited as long as they do not affect the battery reaction, and known ones can be used. In addition, the other components may be used alone or in combination of two or more at any ratio.

[0067] Here, the wetting agent is not particularly limited, and may be an ethylene oxide / propylene oxide surfactant (EO·PO surfactant), a fluorine-based surfactant, a silicon-based surfactant, etc. Among them, it is preferable to use an EO·PO surfactant or a fluorine-based surfactant, and it is more preferable to use an EO·PO surfactant. The content of the wetting agent in the slurry composition for heat-resistant layer is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, preferably 5 parts by mass or less, more preferably 3 parts by mass or less, and even more preferably 1 part by mass or less per 100 parts by mass of non-conductive organic particles. If the content of the wetting agent is 0.05 parts by mass or more per 100 parts by mass of non-conductive organic particles, the wettability to the substrate is improved and the occurrence of repellency is suppressed, so that the coatability of the slurry composition for heat-resistant layer can be further improved. In addition, if the content of the wetting agent is 5 parts by mass or less per 100 parts by mass of non-conductive organic particles, the cycle characteristics of the secondary battery can be improved.

[0068] The non-conductive inorganic particles are not particularly limited as long as they are made of an inorganic material that is stable in the environment in which the secondary battery is used and is electrochemically stable. From this viewpoint, a preferred example of the non-conductive inorganic particles is aluminum oxide (alumina, Al 2 O 3 ), hydrated aluminum oxide (boehmite, AlOOH), gibbsite (Al(OH) 3 ), silicon oxide, magnesium oxide (magnesia), magnesium hydroxide, calcium oxide, titanium oxide (titania), barium titanate (BaTiO 3 ), inorganic oxide particles such as ZrO, alumina-silica composite oxide, etc.; nitride particles such as aluminum nitride, boron nitride, etc.; covalent crystal particles such as silicon, diamond, etc.; sparingly soluble ion crystal particles such as barium sulfate, calcium fluoride, barium fluoride, etc.; clay particles such as talc, montmorillonite, etc. Among these, from the viewpoint of favorably adsorbing the water-soluble polymer and the particulate polymer and improving the adhesion between the heat-resistant layer and the substrate, the non-conductive inorganic particles are preferably particles made of alumina (alumina particles), particles made of boehmite (boehmite particles), and particles made of barium sulfate (barium sulfate particles), and more preferably alumina particles and barium sulfate particles. In addition, these particles may be subjected to element substitution, surface treatment, solid solution, etc., as necessary. In addition, these particles may be used alone or in combination of two or more kinds. The content of the non-conductive inorganic particles in the slurry composition for heat-resistant layer is preferably 600 parts by mass or less, more preferably 400 parts by mass or less, in terms of solid content per 100 parts by mass of non-conductive organic particles, from the viewpoint of further reducing the amount of residual moisture in the heat-resistant layer and improving the cycle characteristics of the secondary battery. The lower limit of the content of the non-conductive inorganic particles in the slurry composition for heat-resistant layer is not particularly limited, but is, for example, 0 parts by mass or more, 100 parts by mass or more, or 200 parts by mass or more, in terms of solid content per 100 parts by mass of non-conductive organic particles.

[0069] In addition, specific examples of the components other than the above-mentioned wetting agent and non-conductive inorganic particles are not particularly limited, but include those described in WO 2012 / 115096.

[0070] <Preparation of Slurry Composition for Non-Aqueous Secondary Battery Heat-Resistant Layer> The slurry composition for heat-resistant layer of the present invention can be prepared by mixing the above-mentioned water-soluble polymer, non-conductive organic particles, water, and any particulate polymer and other components by a known method.Specifically, the slurry composition for heat-resistant layer can be prepared by mixing the above-mentioned components using a mixer such as a ball mill, a sand mill, a bead mill, a pigment disperser, a crusher, an ultrasonic disperser, a homogenizer, a planetary mixer, or a film mix. In addition, when the water-soluble polymer and the non-conductive organic particles, as well as any particulate polymer, are prepared by polymerization in an aqueous solvent, they can be mixed as they are in the form of an aqueous solution or aqueous dispersion to prepare a slurry composition for the heat-resistant layer containing water as a solvent.

[0071] (Heat-resistant layer for non-aqueous secondary batteries) The heat-resistant layer of the present invention is formed from the above-mentioned slurry composition for heat-resistant layer of the present invention, and can be formed, for example, by applying the above-mentioned slurry composition for heat-resistant layer to the surface of a suitable substrate to form a coating film, and then drying the formed coating film. That is, the heat-resistant layer of the present invention is made of the dried product of the above-mentioned slurry composition for heat-resistant layer, and usually contains at least non-conductive organic particles and a water-soluble polymer. Note that each component contained in the heat-resistant layer is contained in the above-mentioned slurry composition for heat-resistant layer, and therefore the preferred ratio of each component is the same as the preferred ratio of each component in the slurry composition for heat-resistant layer. The heat-resistant layer of the present invention is formed from the slurry composition for heat-resistant layer of the present invention, and therefore has excellent heat shrinkage resistance and a small amount of residual moisture.

[0072] <Base material> Here, the substrate to which the slurry composition for heat-resistant layer is applied is not limited, and for example, a coating film of the slurry composition for heat-resistant layer may be formed on the surface of a release substrate, the coating film may be dried to form a heat-resistant layer, and the release substrate may be peeled off from the heat-resistant layer. In this way, the heat-resistant layer peeled off from the release substrate may be used as a free-standing film to form a battery component of a secondary battery. However, from the viewpoint of omitting the step of peeling off the heat-resistant layer and increasing the production efficiency of the battery component, it is preferable to use a separator substrate or an electrode substrate as the substrate. Specifically, it is preferable to apply the slurry composition for the heat-resistant layer onto the separator substrate or the electrode substrate.

[0073] <<Separator substrate>> The separator substrate is not particularly limited, but may be any of known separator substrates such as an organic separator substrate. The organic separator substrate is a porous member made of an organic material, and examples of the organic separator substrate include microporous membranes or nonwoven fabrics containing polyolefin resins such as polyethylene and polypropylene, aromatic polyamide resins, etc., and polyethylene microporous membranes and nonwoven fabrics are preferred because of their excellent strength.

[0074] <<Electrode base material>> The electrode substrate (positive electrode substrate and negative electrode substrate) is not particularly limited, but examples thereof include an electrode substrate in which an electrode mixture layer containing an electrode active material and a binder is formed on a current collector. The current collector, the electrode active material (positive electrode active material, negative electrode active material) and the binder for the electrode mixture layer (binder for the positive electrode mixture layer, binder for the negative electrode mixture layer) in the electrode mixture layer, and the method for forming the electrode mixture layer on the current collector may be any known method, such as that described in JP 2013-145763 A.

[0075] <Method of forming heat-resistant layer> The heat-resistant layer can be formed on a substrate such as the separator substrate or electrode substrate by the following method. 1) A method in which the slurry composition for a heat-resistant layer of the present invention is applied to the surface of a substrate (in the case of an electrode substrate, the surface on the electrode mixture layer side; the same applies below) and then dried; 2) A method of immersing a substrate in the slurry composition for a heat-resistant layer of the present invention and then drying the substrate; and 3) A method in which the slurry composition for a heat-resistant layer of the present invention is applied onto a release substrate, and dried to produce a heat-resistant layer, and the obtained heat-resistant layer is transferred onto the surface of the substrate. Among these, the method 1) is particularly preferred because it is easy to control the thickness of the heat-resistant layer. The method 1) specifically includes a step of applying a slurry composition for a heat-resistant layer onto a substrate (application step) and a step of drying the slurry composition for a heat-resistant layer applied onto the substrate to form a heat-resistant layer (drying step).

[0076] <<Coating process>> In the coating process, the method for coating the slurry composition for the heat-resistant layer onto the substrate is not particularly limited, and examples thereof include a doctor blade method, a reverse roll method, a direct roll method, a gravure method, an extrusion method, and a brush coating method.

[0077] <<Drying process>> In the drying step, the method for drying the slurry composition for the heat-resistant layer on the substrate is not particularly limited and may be any known method. Examples of the drying method include drying with warm air, hot air, or low-humidity air, vacuum drying, and drying by irradiation with infrared rays or electron beams.

[0078] (Non-aqueous secondary battery) The secondary battery of the present invention includes the heat-resistant layer of the present invention described above. More specifically, the secondary battery of the present invention includes a positive electrode, a negative electrode, a separator, and an electrolyte, and the heat-resistant layer is included in at least one of the positive electrode, the negative electrode, and the separator, which are battery components.

[0079] <Positive electrode, negative electrode, and separator> At least one of the positive electrode, negative electrode, and separator used in the secondary battery of the present invention is a battery member having the heat-resistant layer of the present invention described above. Note that the positive electrode, negative electrode, and separator not having the heat-resistant layer of the present invention are not particularly limited, and known positive electrodes, negative electrodes, and separators can be used.

[0080] <Electrolyte> As the electrolyte, an organic electrolyte solution in which a supporting electrolyte is dissolved in an organic solvent is usually used. For example, in a lithium ion secondary battery, a lithium salt is used as the supporting electrolyte. For example, LiPF 6 , LiAsF 6 , LiBF 4 , LiSbF 6 , LiAlCl 4 , LiClO 4 , C.F. 3 SO 3 Li, C. 4 F 9 SO 3 Li, C.F. 3 COOLi, (CF 3 CO) 2 NLi, (CF 3 SO 2 ) 2 NLi, (C 2 F 5 SO 2Among them, LiPF is the most popular because it is easily soluble in solvents and has a high degree of dissociation. 6 , LiClO 4 , C.F. 3 SO 3 Li is preferred. The electrolyte may be used alone or in combination of two or more. Usually, the lithium ion conductivity tends to be higher when a supporting electrolyte with a higher degree of dissociation is used, so the lithium ion conductivity can be adjusted by the type of supporting electrolyte.

[0081] The organic solvent used in the electrolyte is not particularly limited as long as it can dissolve the supporting electrolyte, but for example, in lithium ion secondary batteries, carbonates such as dimethyl carbonate (DMC), ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), butylene carbonate (BC), and ethyl methyl carbonate (EMC); esters such as γ-butyrolactone and methyl formate; ethers such as 1,2-dimethoxyethane and tetrahydrofuran; sulfur-containing compounds such as sulfolane and dimethyl sulfoxide; and the like are preferably used. A mixture of these solvents may also be used. Among them, carbonates are preferred because they have a high dielectric constant and a wide stable potential range. The concentration of the electrolyte in the electrolytic solution can be appropriately adjusted. Known additives may also be added to the electrolytic solution.

[0082] <Method of manufacturing non-aqueous secondary battery> The non-aqueous secondary battery of the present invention can be manufactured, for example, by stacking a positive electrode and a negative electrode with a separator therebetween, wrapping or folding the stack according to the shape of the battery as necessary, placing the stack in a battery container, injecting an electrolyte into the battery container, and sealing the container. At least one of the positive electrode, negative electrode, and separator is a member with a heat-resistant layer. In order to prevent the occurrence of an internal pressure rise in the secondary battery, overcharging and discharging, etc., a fuse, an overcurrent prevention element such as a PTC element, an expanded metal, a lead plate, etc. may be provided as necessary. The shape of the secondary battery may be, for example, any of a coin type, a button type, a sheet type, a cylindrical type, a square type, a flat type, etc. EXAMPLES

[0083] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples. In the following description, "%" and "parts" expressing amounts are based on mass unless otherwise specified. In addition, in a polymer produced by polymerizing a plurality of types of monomers, the ratio of a monomer unit formed by polymerizing a certain monomer in the polymer is usually the same as the ratio (feed ratio) of the certain monomer to the total monomers used in the polymerization of the polymer, unless otherwise specified. In the examples and comparative examples, the weight average molecular weight of the water-soluble polymer, the glass transition temperature and volume average particle size of the non-conductive organic particles and the particulate polymer, the dispersion stability and coatability of the slurry composition for the heat-resistant layer, the moisture content and heat shrinkage resistance of the heat-resistant layer, and the cycle characteristics of the secondary battery were evaluated by the following methods. <Weight average molecular weight of water-soluble polymer> The aqueous solutions containing the water-soluble polymers prepared in the Examples and Comparative Examples were diluted to adjust the concentration to 0.5%. Then, caustic soda was added until the pH reached 10 to 12, and the solution was immersed in a water bath at 80°C or higher for 1 hour, and then diluted to 0.025% with the following eluent to prepare a sample. The sample was analyzed by gel permeation chromatography under the following conditions to determine the weight average molecular weight of the water-soluble polymer. Apparatus: Gel permeation chromatography (GPC) (instrument no. GPC-26) Detector: Differential refractive index detector RI (manufactured by Showa Denko K.K., product name "RI-201", sensitivity 32) Column: 2 TSKgel GMPWXL (φ7.8mm×30cm, Tosoh Corporation) Eluent: 0.1M Tris buffer (pH 9, 0.1M potassium chloride added) Flow rate: 0.7mL / min Column temperature: 40℃ Injection volume: 0.2mL Standard samples: Monodisperse polyethylene oxide (PEO) and polyethylene glycol (PEG) from Tosoh Corporation and Sigma-Aldrich LLC. <Glass transition temperature of non-conductive organic particles and particulate polymers> A powdered sample obtained by drying an aqueous dispersion containing non-conductive organic particles or particulate polymers at a temperature of 25°C for 48 hours was used as the measurement sample. 10 mg of the measurement sample was weighed into an aluminum pan, and measurements were performed under the conditions specified in JIS Z8703 at a temperature rise rate of 20°C / min in the measurement temperature range of -100°C to 200°C using a differential thermal analysis measuring device (manufactured by SII Nano Technology Co., Ltd.), to obtain a differential scanning calorimetry (DSC) curve. An empty aluminum pan was used as a reference. During this temperature rise process, the temperature at which the differential signal (DDSC) showed a peak was determined as the glass transition temperature (°C). When multiple peaks were measured, the temperature showing the peak with the largest displacement was determined as the glass transition temperature of the non-conductive organic particles and particulate polymers. When no peak was confirmed in the measurement temperature range (-100°C to 200°C), the glass transition temperature was determined to be above 200°C. <Volume average particle size of non-conductive organic particles and particulate polymer> The volume average particle diameter of the non-conductive organic particles and particulate polymers was measured by a laser diffraction method. Specifically, the prepared aqueous dispersion containing the non-conductive organic particles or particulate polymers (adjusted to a solid content concentration of 0.1% by mass) was used as a sample. Then, in the particle size distribution (volume basis) measured using a laser diffraction particle size distribution measuring device (manufactured by Beckman Coulter, Inc., product name "LS-13 320"), the particle diameter D50 at which the cumulative volume calculated from the small diameter side becomes 50% was taken as the volume average particle diameter. <Dispersion stability of the slurry composition for heat-resistant layer> 1 kg of the slurry composition for the heat-resistant layer prepared in the examples and comparative examples was placed in a 1 L plastic bottle and left to stand for 10 days. The plastic bottle that had been left to stand was stirred for 30 minutes with a mix rotor. After stirring, the slurry composition for the heat-resistant layer in the plastic bottle was sampled from within the top 1 cm, and the solids concentration of the supernatant sampled was measured. In addition, after stirring, the slurry composition for the heat-resistant layer in the plastic bottle was extracted, and the presence or absence of adhesion to the bottom of the plastic bottle was confirmed, and the evaluation was performed as follows. A: The solids concentration of the supernatant after stirring is 39.5% or more, and there is no adhesion to the bottom of the plastic bottle. B: The solid concentration of the supernatant after stirring is 39.5% or more, but adhesion to the bottom of the plastic bottle is observed. C: The solid concentration of the supernatant after stirring is less than 39.5%. <Coatability of the slurry composition for heat-resistant layer> The appearance of the heat-resistant layers on both sides formed from the slurry composition for heat-resistant layers prepared in the examples and comparative examples was visually observed, and each side was evaluated as follows: The lower evaluation was taken as the overall evaluation of the coatability of the slurry composition for heat-resistant layers. A: An area of ​​30cm x 30cm or more where no clumps, streaks, and / or repellencies are observed. B: The area where no agglomerates, streaks, and / or repellencies are observed is greater than or equal to 10cm x 10cm and less than 30cm x 30cm. C: The area where no clumps, streaks, and / or repellencies are observed is less than 10 cm x 10 cm. <Moisture content of heat-resistant layer> The separators with heat-resistant layers produced in the examples and comparative examples were cut into test pieces measuring 10 cm wide x 10 cm long. The test pieces were left for 24 hours at a temperature of 25°C and a dew point temperature of -60°C. Thereafter, the moisture content of the test pieces was measured by the Karl Fischer method (JIS K-0068 (2001) moisture evaporation method, evaporation temperature 150°C) using a coulometric titration moisture meter, and evaluated according to the following criteria. A smaller moisture content value indicates a lower moisture content in the entire test piece, and in the heat-resistant layer as a whole. A: Moisture content is less than 300 ppm by mass B: Moisture content is 300 mass ppm or more and less than 500 mass ppm C: Moisture content is 500 mass ppm or more <Heat shrink resistance of heat-resistant layer> The separators with heat-resistant layers produced in the Examples and Comparative Examples were cut into squares measuring 12 cm wide x 12 cm long, and a square measuring 10 cm on a side was drawn inside the square to prepare a test piece. The test piece was then placed in a thermostatic chamber at 150°C and left for 1 hour, after which the change in area of ​​the square drawn inside (= {(area of ​​square before being left - area of ​​square after being left) / area of ​​square before being left} x 100%) was calculated as the thermal shrinkage rate and evaluated according to the following criteria. The smaller this thermal shrinkage rate, the better the heat shrinkage resistance of the heat-resistant layer. A: Heat shrinkage rate is less than 10% B: Heat shrinkage rate is 10% or more and less than 20% C: Heat shrinkage rate is 20% or more <Cycle characteristics of secondary batteries> The lithium ion secondary batteries prepared in the examples and comparative examples were left to stand for 24 hours in an environment at 25° C. Thereafter, at 25° C., they were charged to 4.2 V (cutoff condition: 0.02 C) by a constant voltage constant current (CC-CV) method at a charge rate of 1 C, and discharged to 3.0 V by a constant current (CC) method at a discharge rate of 1 C, and the initial capacity C0 was measured. Furthermore, the same charge / discharge operation was repeated in a 25°C environment, and the capacity C1 after 300 cycles was measured. The capacity retention rate ΔC = (C1 / C0) × 100 (%) was calculated and evaluated according to the following criteria. The higher the capacity retention rate, the less the decrease in discharge capacity and the better the cycle characteristics. A: Capacity retention rate ΔC is 85% or more B: Capacity retention rate ΔC is 75% or more and less than 85% C: Capacity retention rate ΔC is less than 75%

[0084] Example 1 <Preparation of an aqueous solution containing a water-soluble polymer> In a 10L flask with a septum, 6335g of ion-exchanged water and 190g of a 2.0% aqueous solution of L-ascorbic acid as a polymerization promoter were charged, and the temperature was heated to 40°C, and the flask was replaced with nitrogen gas at a flow rate of 100mL / min. Next, 939.8g (74.0%) of acrylamide as an amide group-containing monomer, 127.0g (10.0%) of acrylic acid as an acid group-containing monomer, and 203.2g (16.0%) of N-hydroxyethylacrylamide as a hydroxyl group-containing monomer were mixed and injected into the flask with a syringe. Then, 200g of a 5.0% aqueous solution of ammonium persulfate as a polymerization initiator was added to the flask with a syringe, and the reaction temperature was set to 60°C. After 2 hours, in order to further increase the reaction conversion rate, 100g of a 5.0% aqueous solution of ammonium persulfate as a polymerization initiator and 95g of a 2.0% aqueous solution of L-ascorbic acid as a polymerization promoter were added. After another 2 hours, 100g of a 5.0% aqueous solution of ammonium persulfate as a polymerization initiator and 95g of a 2.0% aqueous solution of L-ascorbic acid as a polymerization promoter were added. After 2 hours, 34g of a 5% aqueous solution of sodium nitrite as a reaction terminator was added to the flask and stirred. Thereafter, the flask was cooled to 40°C to create an air atmosphere, and an 8% aqueous solution of lithium hydroxide was used to set the pH of the system to 8.0 to prepare an aqueous solution containing a water-soluble polymer. The weight average molecular weight of the resulting water-soluble polymer was then measured, and the results are shown in Table 1. <Preparation of aqueous dispersion containing non-conductive organic particles> In a reactor A equipped with a stirrer, 0.1 parts of sodium dodecylbenzenesulfonate, 0.3 parts of ammonium persulfate, and 100 parts of ion-exchanged water were added, mixed to form a mixture, and heated to 80°C. Meanwhile, in another container, 100 parts of n-butyl acrylate as a (meth)acrylic acid ester monomer, 0.8 parts of sodium dodecylbenzenesulfonate, and 100 parts of ion-exchanged water were mixed to prepare a monomer composition for seed particles. This monomer composition for seed particles was continuously added to the above-mentioned reactor A over a period of 4 hours to carry out a polymerization reaction. The temperature inside the reactor during the continuous addition of the monomer composition for seed particles was maintained at 80°C. After the continuous addition was completed, the polymerization reaction was continued for another 3 hours at 90°C. As a result, an aqueous dispersion of seed particles was obtained. The volume average particle diameter of the seed particles was measured in the same manner as in the measurement method of the above-mentioned "volume average particle diameter of non-conductive organic particles and particulate polymers", and was 120 nm. Next, the above-mentioned aqueous dispersion of seed particles (16 parts of n-butyl acrylate in terms of solid content), 82 parts of ethylene glycol dimethacrylate (manufactured by Kyoeisha Chemical Co., Ltd., product name "Light Ester EG") as a crosslinkable monomer, 2 parts of acrylic acid as a hydrophilic group-containing monomer, 2.5 parts of sodium dodecylbenzenesulfonate, 4.0 parts of t-butylperoxy-2-ethylhexanoate (manufactured by NOF Corporation, product name "Perbutyl O") as a polymerization initiator, and 200 parts of ion-exchanged water were added to a reactor equipped with a stirrer, and the mixture was stirred at 35°C for 12 hours, thereby allowing the crosslinkable monomer, hydrophilic group-containing monomer, and polymerization initiator to be completely absorbed into the seed particles. Thereafter, the temperature inside the reactor was maintained at 90°C, and a polymerization reaction (seed polymerization) was carried out for 5 hours. Next, steam was introduced to remove unreacted monomers and initiator decomposition products, and an aqueous dispersion containing non-conductive organic particles was obtained. The glass transition temperature and volume average particle size of the obtained non-conductive organic particles were then measured. The results are shown in Table 1. <Preparation of aqueous dispersion containing particulate polymer> To a reactor equipped with a stirrer, 70 parts of ion-exchanged water, 0.15 parts of sodium dodecylbenzenesulfonate as an emulsifier, and 0.5 parts of ammonium persulfate were fed, the gas phase was replaced with nitrogen gas, and the temperature was raised to 70°C. Meanwhile, in another vessel, 50 parts of ion-exchanged water, 0.8 parts of sodium dodecylbenzenesulfonate, 94.2 parts of n-butyl acrylate as a (meth)acrylic acid ester monomer, 2 parts of methacrylic acid as a hydrophilic group-containing monomer, 0.3 parts of allyl methacrylate and 1.5 parts of allyl glycidyl ether as crosslinkable monomers, and 2 parts of acrylonitrile as other monomers were mixed to obtain a monomer composition. This monomer composition was continuously added to the above reactor over 4 hours to carry out polymerization. During the addition, the reaction was carried out at 70°C. After the addition was completed, the mixture was stirred at 80°C for another 3 hours to terminate the reaction, and an aqueous dispersion containing a particulate polymer was obtained. The glass transition temperature and volume average particle size of the resulting particulate polymer were measured, and the results are shown in Table 1. <Preparation of Slurry Composition for Non-Aqueous Secondary Battery Heat-Resistant Layer> A slurry composition for a heat-resistant layer with a solids concentration of 15% was prepared by mixing 100 parts in terms of solids of the aqueous dispersion containing the non-conductive organic particles prepared as described above, 6 parts in terms of solids of an aqueous dispersion containing a particulate polymer, 4 parts in terms of solids of an aqueous solution containing a water-soluble polymer, and 0.8 parts of an ethylene oxide / propylene oxide surfactant (manufactured by San Nopco Ltd., product name "Noptex ED-052") as a wetting agent. The dispersion stability and coatability of the thus obtained slurry composition for the heat-resistant layer were evaluated, and the results are shown in Table 1. <Preparation of separator> A polyethylene separator substrate (manufactured by Asahi Kasei Corporation, product name "ND407", thickness: 7 μm) was prepared. The slurry composition for heat-resistant layer prepared above was applied to the surface of the prepared separator substrate and dried at a temperature of 50° C. for 3 minutes. Next, the slurry composition for heat-resistant layer was similarly applied to the uncoated surface and dried to obtain a separator with heat-resistant layers on both sides (thickness of heat-resistant layer: 1.5 μm per side). The moisture content and heat shrinkage resistance of the heat-resistant layer thus obtained were evaluated, and the results are shown in Table 1. <Formation of the negative electrode> In a 5MPa pressure vessel equipped with a stirrer, 33 parts of 1,3-butadiene as an aliphatic conjugated diene monomer, 3.5 parts of itaconic acid as a carboxylic acid group-containing monomer, 63.5 parts of styrene as an aromatic vinyl monomer, 0.4 parts of sodium dodecylbenzenesulfonate as an emulsifier, 150 parts of ion-exchanged water, and 0.5 parts of potassium persulfate as a polymerization initiator were placed, thoroughly stirred, and then heated to 50°C to initiate polymerization. When the polymerization conversion rate reached 96%, the mixture was cooled to stop the polymerization reaction, and a mixture containing a particulate binder (styrene-butadiene copolymer) was obtained. After adjusting the pH to 8 by adding a 5% aqueous sodium hydroxide solution to the mixture, the unreacted monomer was removed by heating and vacuum distillation. The mixture was then cooled to 30°C or less to obtain an aqueous dispersion containing a binder for the negative electrode. Into a planetary mixer, 48.75 parts of artificial graphite (theoretical capacity: 360 mAh / g) and 48.75 parts of natural graphite (theoretical capacity: 360 mAh / g) as negative electrode active materials, and 1 part of carboxymethyl cellulose (solid content equivalent) as a thickener were added. Further, the mixture was diluted with ion-exchanged water so that the solid content concentration was 60%, and then kneaded for 60 minutes at a rotation speed of 45 rpm. Then, 1.5 parts of the aqueous dispersion containing the negative electrode binder obtained as described above was added in terms of solid content, and kneaded for 40 minutes at a rotation speed of 40 rpm. Then, ion-exchanged water was added so that the viscosity was 3000±500 mPa·s (measured with a B-type viscometer at 25°C and 60 rpm), thereby preparing a slurry composition for a negative electrode mixture layer. The above-mentioned slurry composition for the negative electrode mixture layer was applied to the surface of a 15 μm-thick copper foil current collector with a comma coater in an amount of 11±0.5 mg / cm 2 Thereafter, the copper foil coated with the slurry composition for the negative electrode composite layer was transported at a speed of 400 mm / min through an oven at a temperature of 80° C. for 2 minutes and then through an oven at a temperature of 110° C. for 2 minutes to dry the slurry composition on the copper foil, thereby obtaining a negative electrode raw sheet in which a negative electrode composite layer was formed on a current collector. Thereafter, the negative electrode composite layer side of the produced negative electrode blank was roll-pressed under conditions of a temperature of 25±3°C and a linear pressure of 11 t (tons) to obtain a negative electrode composite layer density of 1.60 g / cm 3 Thereafter, the negative electrode was left for one week in an environment of a temperature of 25±3° C. and a relative humidity of 50±5%. <Formation of the positive electrode> The planetary mixer is equipped with a lithium composite oxide material NMC111 (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 A slurry composition for a positive electrode composite layer was prepared by adding 96 parts of ethylenediaminetetraacetate (manufactured by Denka Co., Ltd., product name "HS-100") as a conductive material, 2 parts of acetylene black (manufactured by Kureha Chemical Co., Ltd., product name "KF-1100") as a positive electrode binder, and further adding and mixing N-methyl-2-pyrrolidone (NMP) as a dispersion medium to give a total solids concentration of 67%. Next, the obtained slurry composition for the positive electrode mixture layer was applied to an aluminum foil having a thickness of 20 μm, which was a current collector, with a comma coater in an amount of 20±0.5 mg / cm. 2 The coating was applied so that the result was as follows. The slurry composition on the aluminum foil was dried by transporting the aluminum foil at a speed of 200 mm / min through an oven at a temperature of 90° C. for 2 minutes and then through an oven at a temperature of 120° C. for 2 minutes, thereby obtaining a positive electrode raw sheet in which a positive electrode composite layer was formed on the current collector. Thereafter, the positive electrode composite layer side of the prepared positive electrode blank was roll-pressed under conditions of a temperature of 25±3°C and a linear pressure of 14 tonnes, so that the density of the positive electrode composite layer became 3.40 g / cm 3 Thereafter, the positive electrode was left for one week in an environment of a temperature of 25±3° C. and a relative humidity of 50±5%. <Production of lithium-ion secondary battery> A wound cell (discharge capacity equivalent to 520 mAh) was prepared using the negative electrode, positive electrode, and separator described above, and placed in an aluminum package. Then, 1.0 M LiPF 2 was placed in the aluminum package as an electrolyte. 6A solution (solvent: mixed solvent of ethylene carbonate (EC) / diethyl carbonate (DEC) = 3 / 7 (volume ratio), additive: containing 2 volume% (solvent ratio) of vinylene carbonate) was filled in. Furthermore, in order to seal the opening of the aluminum packaging material, the aluminum packaging material was closed by heat sealing at a temperature of 150°C, and a lithium ion secondary battery was produced. The cycle characteristics were evaluated using this lithium ion secondary battery. The results are shown in Table 1.

[0085] Example 2 In preparing the aqueous solution containing the water-soluble polymer, the amount of acrylamide as an amide group-containing monomer was changed to 889.0 g (70.0%), the amount of acrylic acid as an acid group-containing monomer was changed to 152.4 g (12.0%), and the amount of N-hydroxyethylacrylamide as a hydroxyl group-containing monomer was changed to 228.6 g (18.0%). In the same manner as in Example 1, an aqueous solution containing a water-soluble polymer, an aqueous dispersion containing non-conductive organic particles, an aqueous dispersion containing a particulate polymer, a slurry composition for a heat-resistant layer, a negative electrode, a positive electrode, a separator, and a lithium ion secondary battery were prepared or produced. Then, evaluation was performed in the same manner as in Example 1. The results are shown in Table 1.

[0086] Example 3 In preparing the aqueous solution containing the water-soluble polymer, the amount of acrylamide as an amide group-containing monomer was changed to 825.5 g (65.0%), the amount of acrylic acid as an acid group-containing monomer was changed to 139.7 g (11.0%), and the amount of N-hydroxyethylacrylamide as a hydroxyl group-containing monomer was changed to 304.8 g (24.0%). In the same manner as in Example 1, an aqueous solution containing a water-soluble polymer, an aqueous dispersion containing non-conductive organic particles, an aqueous dispersion containing a particulate polymer, a slurry composition for a heat-resistant layer, a negative electrode, a positive electrode, a separator, and a lithium ion secondary battery were prepared or produced. Then, evaluation was performed in the same manner as in Example 1. The results are shown in Table 1.

[0087] Example 4 In preparing the aqueous solution containing the water-soluble polymer, the amount of acrylamide as an amide group-containing monomer was changed to 825.5 g (65.0%), the amount of acrylic acid as an acid group-containing monomer was changed to 38.1 g (3.0%), and the amount of N-hydroxyethylacrylamide as a hydroxyl group-containing monomer was changed to 406.4 g (32.0%). In the same manner as in Example 1, an aqueous solution containing a water-soluble polymer, an aqueous dispersion containing non-conductive organic particles, an aqueous dispersion containing a particulate polymer, a slurry composition for a heat-resistant layer, a negative electrode, a positive electrode, a separator, and a lithium ion secondary battery were prepared or produced. Then, evaluation was performed in the same manner as in Example 1. The results are shown in Table 1.

[0088] Example 5 In preparing the aqueous solution containing the water-soluble polymer, the amount of acrylamide as an amide group-containing monomer was changed to 806.45g (63.5%), the amount of acrylic acid as an acid group-containing monomer was changed to 215.9g (17.0%), and the amount of N-hydroxyethylacrylamide as a hydroxyl group-containing monomer was changed to 247.65g (19.5%). In the same manner as in Example 1, an aqueous solution containing a water-soluble polymer, an aqueous dispersion containing non-conductive organic particles, an aqueous dispersion containing a particulate polymer, a slurry composition for a heat-resistant layer, a negative electrode, a positive electrode, a separator, and a lithium ion secondary battery were prepared or produced. Then, evaluation was performed in the same manner as in Example 1. The results are shown in Table 1.

[0089] Example 6 In preparing the aqueous solution containing the water-soluble polymer, the amount of acrylamide as an amide group-containing monomer was changed to 1219.2 g (96.0%), the amount of acrylic acid as an acid group-containing monomer was changed to 17.78 g (1.4%), and the amount of N-hydroxyethylacrylamide as a hydroxyl group-containing monomer was changed to 33.02 g (2.6%). In the same manner as in Example 1, an aqueous solution containing a water-soluble polymer, an aqueous dispersion containing non-conductive organic particles, an aqueous dispersion containing a particulate polymer, a slurry composition for a heat-resistant layer, a negative electrode, a positive electrode, a separator, and a lithium ion secondary battery were prepared or produced. Then, evaluation was performed in the same manner as in Example 1. The results are shown in Table 1.

[0090] Example 7 In preparing the aqueous solution containing the water-soluble polymer, the amount of acrylamide as an amide group-containing monomer was changed to 939.8 g (74.0%), the amount of acrylic acid as an acid group-containing monomer was changed to 203.2 g (16.0%), and the amount of N-hydroxyethylacrylamide as a hydroxyl group-containing monomer was changed to 127.0 g (10.0%). In the same manner as in Example 1, an aqueous solution containing a water-soluble polymer, an aqueous dispersion containing non-conductive organic particles, an aqueous dispersion containing a particulate polymer, a slurry composition for a heat-resistant layer, a negative electrode, a positive electrode, a separator, and a lithium ion secondary battery were prepared or produced. Then, evaluation was performed in the same manner as in Example 1. The results are shown in Table 1.

[0091] Example 8 In preparing the aqueous solution containing the water-soluble polymer, the amount of acrylamide as an amide group-containing monomer was changed to 939.8 g (74.0%), the amount of acrylic acid as an acid group-containing monomer was changed to 63.5 g (5.0%), and the amount of N-hydroxyethylacrylamide as a hydroxyl group-containing monomer was changed to 266.7 g (21.0%). In the same manner as in Example 1, an aqueous solution containing a water-soluble polymer, an aqueous dispersion containing non-conductive organic particles, an aqueous dispersion containing a particulate polymer, a slurry composition for a heat-resistant layer, a negative electrode, a positive electrode, a separator, and a lithium ion secondary battery were prepared or produced. Then, evaluation was performed in the same manner as in Example 1. The results are shown in Table 1.

[0092] Example 9 Except for using the aqueous dispersion containing non-conductive organic particles prepared as follows, an aqueous solution containing a water-soluble polymer, an aqueous dispersion containing a particulate polymer, a slurry composition for a heat-resistant layer, a negative electrode, a positive electrode, a separator, and a lithium ion secondary battery were prepared or produced in the same manner as in Example 1. Evaluations were then performed in the same manner as in Example 1. The results are shown in Table 1. <Preparation of aqueous dispersion containing non-conductive organic particles> In a reactor A equipped with a stirrer, 0.1 parts of sodium dodecylbenzenesulfonate, 0.3 parts of ammonium persulfate, and 100 parts of ion-exchanged water were added, mixed to form a mixture, and the mixture was heated to 80°C. Meanwhile, in another container, 100 parts of n-butyl acrylate as a (meth)acrylic acid ester monomer, 0.6 parts of sodium dodecylbenzenesulfonate, and 100 parts of ion-exchanged water were mixed to prepare a monomer composition for seed particles. This monomer composition for seed particles was continuously added to the above-mentioned reactor A over a period of 4 hours to carry out a polymerization reaction. The temperature inside the reactor during the continuous addition of the monomer composition for seed particles was maintained at 80°C. After the continuous addition was completed, the polymerization reaction was continued for another 3 hours at 90°C. As a result, an aqueous dispersion of seed particles was obtained. The volume average particle diameter of the seed particles was measured in the same manner as in the measurement method of the above-mentioned "volume average particle diameter of non-conductive organic particles and particulate polymers", and was 160 nm. Next, the above-mentioned aqueous dispersion of seed particles (48 parts of n-butyl acrylate in terms of solid content), 50 parts of ethylene glycol dimethacrylate (manufactured by Kyoeisha Chemical Co., Ltd., product name "Light Ester EG") as a crosslinkable monomer, 2 parts of acrylic acid as a hydrophilic group-containing monomer, 2.5 parts of sodium dodecylbenzenesulfonate, 4.0 parts of t-butylperoxy-2-ethylhexanoate (manufactured by NOF Corporation, product name "Perbutyl O") as a polymerization initiator, and 200 parts of ion-exchanged water were added to a reactor equipped with a stirrer, and the mixture was stirred at 35°C for 12 hours, thereby allowing the crosslinkable monomer, hydrophilic group-containing monomer, and polymerization initiator to be completely absorbed into the seed particles. Thereafter, the temperature in the reactor was maintained at 90°C, and a polymerization reaction (seed polymerization) was carried out for 5 hours. Next, steam was introduced to remove unreacted monomers and initiator decomposition products, to obtain an aqueous dispersion containing non-conductive organic particles.

[0093] Example 10 Except for using the aqueous dispersion containing non-conductive organic particles prepared as follows, an aqueous solution containing a water-soluble polymer, an aqueous dispersion containing a particulate polymer, a slurry composition for a heat-resistant layer, a negative electrode, a positive electrode, a separator, and a lithium ion secondary battery were prepared or produced in the same manner as in Example 1. Evaluations were then performed in the same manner as in Example 1. The results are shown in Table 1. <Preparation of aqueous dispersion containing non-conductive organic particles> In a reactor A equipped with a stirrer, 0.1 parts of sodium dodecylbenzenesulfonate, 0.3 parts of ammonium persulfate, and 100 parts of ion-exchanged water were added, mixed to form a mixture, and heated to 80°C. Meanwhile, in another container, 100 parts of n-butyl acrylate as a (meth)acrylic acid ester monomer, 0.4 parts of sodium dodecylbenzenesulfonate, and 100 parts of ion-exchanged water were mixed to prepare a monomer composition for seed particles. This monomer composition for seed particles was continuously added to the above-mentioned reactor A over a period of 4 hours to carry out a polymerization reaction. The temperature inside the reactor during the continuous addition of the monomer composition for seed particles was maintained at 80°C. After the continuous addition was completed, the polymerization reaction was continued for another 3 hours at 90°C. As a result, an aqueous dispersion of seed particles was obtained. The volume average particle diameter of the seed particles was measured in the same manner as in the measurement method of the above-mentioned "volume average particle diameter of non-conductive organic particles and particulate polymers", and was found to be 200 nm. Next, the above-mentioned aqueous dispersion of seed particles (73 parts of n-butyl acrylate in terms of solid content), 25 parts of ethylene glycol dimethacrylate (manufactured by Kyoeisha Chemical Co., Ltd., product name "Light Ester EG") as a crosslinkable monomer, 2 parts of acrylic acid as a hydrophilic group-containing monomer, 2.5 parts of sodium dodecylbenzenesulfonate, 4.0 parts of t-butylperoxy-2-ethylhexanoate (manufactured by NOF Corporation, product name "Perbutyl O") as a polymerization initiator, and 200 parts of ion-exchanged water were added to a reactor equipped with a stirrer, and the mixture was stirred at 35°C for 12 hours, thereby allowing the crosslinkable monomer, hydrophilic group-containing monomer, and polymerization initiator to be completely absorbed into the seed particles. Thereafter, the temperature in the reactor was maintained at 90°C, and a polymerization reaction (seed polymerization) was carried out for 5 hours. Next, steam was introduced to remove unreacted monomers and initiator decomposition products, to obtain an aqueous dispersion containing non-conductive organic particles.

[0094] Example 11 Except for using the aqueous dispersion containing non-conductive organic particles prepared as follows, an aqueous solution containing a water-soluble polymer, an aqueous dispersion containing a particulate polymer, a slurry composition for a heat-resistant layer, a negative electrode, a positive electrode, a separator, and a lithium ion secondary battery were prepared or produced in the same manner as in Example 1. Evaluations were then performed in the same manner as in Example 1. The results are shown in Table 2. <Preparation of aqueous dispersion containing non-conductive organic particles> In a reactor A equipped with a stirrer, 0.3 parts of sodium dodecylbenzenesulfonate, 0.5 parts of ammonium persulfate, and 100 parts of ion-exchanged water were added, mixed to form a mixture, and heated to 80°C. Meanwhile, in another container, 100 parts of n-butyl acrylate as a (meth)acrylic acid ester monomer, 1.2 parts of sodium dodecylbenzenesulfonate, and 100 parts of ion-exchanged water were mixed to prepare a monomer composition for seed particles. This monomer composition for seed particles was continuously added to the above-mentioned reactor A over a period of 4 hours to carry out a polymerization reaction. The temperature inside the reactor during the continuous addition of the monomer composition for seed particles was maintained at 80°C. After the continuous addition was completed, the polymerization reaction was continued for another 3 hours at 90°C. As a result, an aqueous dispersion of seed particles was obtained. The volume average particle diameter of the seed particles was measured in the same manner as in the measurement method of the above-mentioned "volume average particle diameter of non-conductive organic particles and particulate polymers", and was 60 nm. Next, the above-mentioned aqueous dispersion of seed particles (5 parts of n-butyl acrylate in terms of solid content), 93 parts of ethylene glycol dimethacrylate (manufactured by Kyoeisha Chemical Co., Ltd., product name "Light Ester EG") as a crosslinkable monomer, 2 parts of acrylic acid as a hydrophilic group-containing monomer, 2.5 parts of sodium dodecylbenzenesulfonate, 4.0 parts of t-butylperoxy-2-ethylhexanoate (manufactured by NOF Corporation, product name "Perbutyl O") as a polymerization initiator, and 200 parts of ion-exchanged water were added to a reactor equipped with a stirrer, and the mixture was stirred at 35°C for 12 hours, thereby allowing the crosslinkable monomer, hydrophilic group-containing monomer, and polymerization initiator to be completely absorbed into the seed particles. Thereafter, the temperature in the reactor was maintained at 90°C, and a polymerization reaction (seed polymerization) was carried out for 5 hours. Next, steam was introduced to remove unreacted monomers and initiator decomposition products, to obtain an aqueous dispersion containing non-conductive organic particles.

[0095] Example 12 Except for using the aqueous dispersion containing non-conductive organic particles prepared as follows, an aqueous solution containing a water-soluble polymer, an aqueous dispersion containing a particulate polymer, a slurry composition for a heat-resistant layer, a negative electrode, a positive electrode, a separator, and a lithium ion secondary battery were prepared or produced in the same manner as in Example 1. Evaluations were then performed in the same manner as in Example 1. The results are shown in Table 2. <Preparation of aqueous dispersion containing non-conductive organic particles> In a reactor A equipped with a stirrer, 0.5 parts of sodium dodecylbenzenesulfonate, 0.5 parts of ammonium persulfate, and 100 parts of ion-exchanged water were added, mixed to form a mixture, and heated to 80°C. Meanwhile, in another container, 100 parts of n-butyl acrylate as a (meth)acrylic acid ester monomer, 1.2 parts of sodium dodecylbenzenesulfonate, and 100 parts of ion-exchanged water were mixed to prepare a monomer composition for seed particles. This monomer composition for seed particles was continuously added to the above-mentioned reactor A over a period of 4 hours to carry out a polymerization reaction. The temperature inside the reactor during the continuous addition of the monomer composition for seed particles was maintained at 80°C. After the continuous addition was completed, the polymerization reaction was continued for another 3 hours at 90°C. As a result, an aqueous dispersion of seed particles was obtained. The volume average particle diameter of the seed particles was measured in the same manner as in the measurement method of the above-mentioned "volume average particle diameter of non-conductive organic particles and particulate polymers", and was 50 nm. Next, the above-mentioned aqueous dispersion of seed particles (16 parts of n-butyl acrylate in terms of solid content), 82 parts of ethylene glycol dimethacrylate (manufactured by Kyoeisha Chemical Co., Ltd., product name "Light Ester EG") as a crosslinkable monomer, 2 parts of acrylic acid as a hydrophilic group-containing monomer, 2.5 parts of sodium dodecylbenzenesulfonate, 4.0 parts of t-butylperoxy-2-ethylhexanoate (manufactured by NOF Corporation, product name "Perbutyl O") as a polymerization initiator, and 200 parts of ion-exchanged water were added to a reactor equipped with a stirrer, and the mixture was stirred at 35°C for 12 hours, thereby allowing the crosslinkable monomer, hydrophilic group-containing monomer, and polymerization initiator to be completely absorbed into the seed particles. Thereafter, the temperature inside the reactor was maintained at 90°C, and a polymerization reaction (seed polymerization) was carried out for 5 hours. Next, steam was introduced to remove unreacted monomers and initiator decomposition products, to obtain an aqueous dispersion containing non-conductive organic particles.

[0096] Example 13 In preparing the aqueous solution containing the water-soluble polymer, except that 2-hydroxyethyl methacrylate was used instead of N-hydroxyethyl acrylamide as the hydroxyl group-containing monomer, an aqueous solution containing the water-soluble polymer, an aqueous dispersion containing non-conductive organic particles, an aqueous dispersion containing a particulate polymer, a slurry composition for a heat-resistant layer, a negative electrode, a positive electrode, a separator, and a lithium ion secondary battery were prepared or produced in the same manner as in Example 1. Then, evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0097] Comparative Example 1 Except for using the aqueous solution containing the water-soluble polymer prepared as follows, the aqueous dispersion containing non-conductive organic particles, the aqueous dispersion containing the particulate polymer, the slurry composition for the heat-resistant layer, the negative electrode, the positive electrode, the separator, and the lithium ion secondary battery were prepared or produced in the same manner as in Example 1. Then, evaluations were performed in the same manner as in Example 1. The results are shown in Table 2. <Preparation of an aqueous solution containing a water-soluble polymer> In a 10L flask with a septum, a monomer composition consisting of 895.0g (89.5%) acrylamide and 15.0g (1.5%) dimethylacrylamide as amide group-containing monomers, and 90.0g (9.0%) acrylic acid as an acid group-containing monomer, as well as 3650g ion-exchanged water and 50g isopropyl alcohol were charged, and the atmosphere in the flask was replaced with nitrogen gas at a flow rate of 100mL / min. Next, 70g of a 5% aqueous solution of ammonium persulfate and 30g of a 5% aqueous solution of sodium hydrogen sulfite as polymerization initiators were added to the flask under stirring, and the temperature was raised from room temperature to 80°C and kept at that temperature for 3 hours. Then, 1620g of ion-exchanged water was added, and the pH was adjusted to 8 with a 10% aqueous solution of sodium hydroxide to obtain an aqueous solution containing a water-soluble polymer.

[0098] Comparative Example 2 In preparing the aqueous solution containing the water-soluble polymer, acrylic acid as an acid group-containing monomer and N-hydroxyethylacrylamide as a hydroxyl group-containing monomer were not added, and the amount of acrylamide as an amide group-containing monomer was changed to 1270 g (100%), but the aqueous solution containing the water-soluble polymer, the aqueous dispersion containing non-conductive organic particles, the aqueous dispersion containing a particulate polymer, the slurry composition for the heat-resistant layer, the negative electrode, the positive electrode, the separator, and the lithium ion secondary battery were prepared or produced in the same manner as in Example 1. Then, evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0099] Comparative Example 3 Except for using the aqueous solution containing the water-soluble polymer prepared as follows, the aqueous dispersion containing non-conductive organic particles, the aqueous dispersion containing the particulate polymer, the slurry composition for the heat-resistant layer, the negative electrode, the positive electrode, the separator, and the lithium ion secondary battery were prepared or produced in the same manner as in Example 1. Then, evaluations were performed in the same manner as in Example 1. The results are shown in Table 2. <Preparation of an aqueous solution containing a water-soluble polymer> In a 10 L flask with a septum, 6335 g of ion-exchanged water and 95 g of a 2.0% aqueous solution of L-ascorbic acid as a polymerization promoter were charged, and the mixture was heated to 40° C., and the atmosphere in the flask was replaced with nitrogen gas at a flow rate of 100 mL / min. Next, 635.0 g (50.0%) of acrylamide and 127.0 g (10.0%) of methacrylamide as amide group-containing monomers, 317.5 g (25.0%) of acrylic acid and 63.5 g (5.0%) of 2-acrylamido-2-methylpropanesulfonic acid as acid group-containing monomers, 63.5 g (5.0%) of 2-hydroxyethyl methacrylate as a hydroxyl group-containing monomer, and 63.5 g (5.0%) of methacrylonitrile as other monomers were mixed and injected into the flask with a syringe. Then, 100g of a 5.0% aqueous solution of ammonium persulfate as a polymerization initiator was added to the flask with a syringe, and the reaction temperature was set to 60°C. After 2 hours, in order to further increase the reaction conversion rate, 50g of a 5.0% aqueous solution of ammonium persulfate as a polymerization initiator and 47.5g of a 2.0% aqueous solution of L-ascorbic acid as a polymerization promoter were added. After another 2 hours, 50g of a 5.0% aqueous solution of ammonium persulfate as a polymerization initiator and 47.5g of a 2.0% aqueous solution of L-ascorbic acid as a polymerization promoter were added. After 2 hours, 34g of a 5% aqueous solution of sodium nitrite as a reaction terminator was added to the flask and stirred. Then, the flask was cooled to 40°C to create an air atmosphere, and an 8% aqueous solution of lithium hydroxide was used to set the pH of the system to 8.0 to prepare an aqueous solution containing a water-soluble polymer.

[0100] Comparative Example 4 Except for using the aqueous solution containing the water-soluble polymer prepared as follows, the aqueous dispersion containing non-conductive organic particles, the aqueous dispersion containing the particulate polymer, the slurry composition for the heat-resistant layer, the negative electrode, the positive electrode, the separator, and the lithium ion secondary battery were prepared or produced in the same manner as in Example 1. Then, evaluations were performed in the same manner as in Example 1. The results are shown in Table 2. <Preparation of an aqueous solution containing a water-soluble polymer> In a 10L flask with a septum, 6335g of ion-exchanged water and 95g of a 2.0% aqueous solution of L-ascorbic acid as a polymerization promoter were charged, and the temperature was heated to 40°C, and the flask was replaced with nitrogen gas at a flow rate of 100mL / min. Next, 571.5g (45.0%) of acrylamide as an amide group-containing monomer, 317.5g (25.0%) of acrylic acid as an acid group-containing monomer, and 381.0g (30.0%) of N-hydroxyethylacrylamide as a hydroxyl group-containing monomer were mixed and injected into the flask with a syringe. Then, 100g of a 5.0% aqueous solution of ammonium persulfate as a polymerization initiator was added to the flask with a syringe, and the reaction temperature was set to 60°C. After 2 hours, in order to further increase the reaction conversion rate, 50g of a 5.0% aqueous solution of ammonium persulfate as a polymerization initiator and 47.5g of a 2.0% aqueous solution of L-ascorbic acid as a polymerization promoter were added. After another 2 hours, 50g of a 5.0% aqueous solution of ammonium persulfate as a polymerization initiator and 47.5g of a 2.0% aqueous solution of L-ascorbic acid as a polymerization promoter were added. After 2 hours, 34g of a 5% aqueous solution of sodium nitrite as a reaction terminator was added to the flask and stirred. Then, the flask was cooled to 40°C to create an air atmosphere, and an 8% aqueous solution of lithium hydroxide was used to adjust the pH of the system to 8.0 to prepare an aqueous solution containing a water-soluble polymer.

[0101] Comparative Example 5 In preparing the aqueous solution containing the water-soluble polymer, the amount of acrylamide as an amide group-containing monomer was changed to 946.15 g (74.5%), the amount of acrylic acid as an acid group-containing monomer was changed to 6.35 g (0.5%), and the amount of N-hydroxyethylacrylamide as a hydroxyl group-containing monomer unit was changed to 317.5 g (25.0%). In the same manner as in Example 1, an aqueous solution containing a water-soluble polymer, an aqueous dispersion containing non-conductive organic particles, an aqueous dispersion containing a particulate polymer, a slurry composition for a heat-resistant layer, a negative electrode, a positive electrode, a separator, and a lithium ion secondary battery were prepared or produced. Then, evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0102] Comparative Example 6 In preparing the slurry composition for the heat-resistant layer, 100 parts (solids equivalent) of an aqueous dispersion containing non-conductive inorganic particles prepared as described below was used instead of 100 parts (solids equivalent) of an aqueous dispersion containing non-conductive organic particles, and the amount of the aqueous solution containing a water-soluble polymer added was changed from 4 parts to 2 parts. Otherwise, an aqueous solution containing a water-soluble polymer, an aqueous dispersion containing a particulate polymer, a slurry composition for the heat-resistant layer, a negative electrode, a positive electrode, a separator, and a lithium ion secondary battery were prepared or produced in the same manner as in Example 1. Then, evaluation was performed in the same manner as in Example 1. The results are shown in Table 2. <Preparation of aqueous dispersion containing non-conductive inorganic particles> Alumina particles (manufactured by Sumitomo Chemical Co., Ltd., product name "AKP-30", volume average particle size: 0.3 μm) were prepared as non-conductive inorganic particles, and sodium polyacrylate (manufactured by Toa Gosei Co., Ltd., product name "Aron T-50") was prepared as a dispersant. 100 parts of non-conductive inorganic particles, 0.5 parts of dispersant, and ion-exchanged water were mixed and processed for 1 hour in a bead mill (manufactured by Ashizawa Finetech Co., Ltd., product name "LMZ015") to obtain an aqueous dispersion containing non-conductive inorganic particles.

[0103] Comparative Example 7 Except for using the aqueous dispersion containing non-conductive organic particles prepared as follows, an aqueous solution containing a water-soluble polymer, an aqueous dispersion containing a particulate polymer, a slurry composition for a heat-resistant layer, a negative electrode, a positive electrode, a separator, and a lithium ion secondary battery were prepared or produced in the same manner as in Example 1. Evaluations were then performed in the same manner as in Example 1. The results are shown in Table 2. <Preparation of aqueous dispersion containing non-conductive organic particles> In a reactor A equipped with a stirrer, 0.1 parts of sodium dodecylbenzenesulfonate, 0.3 parts of ammonium persulfate, and 100 parts of ion-exchanged water were added, mixed to form a mixture, and the temperature was raised to 75°C. Meanwhile, in another vessel, 93 parts of methyl methacrylate as a (meth)acrylic acid ester monomer, 5 parts of ethylene glycol dimethacrylate (manufactured by Kyoeisha Chemical Co., Ltd., product name "Light Ester EG") as a crosslinkable monomer, 2 parts of acrylic acid as a hydrophilic group-containing monomer, 0.4 parts of sodium dodecylbenzenesulfonate, and 100 parts of ion-exchanged water were mixed to prepare a monomer composition for non-conductive organic particles. This monomer composition for non-conductive organic particles was continuously added to the above-mentioned reactor A over a period of 4 hours to carry out a polymerization reaction. The temperature inside the reactor during the continuous addition of the monomer composition for non-conductive organic particles was maintained at 75°C. After the completion of the continuous addition, the polymerization reaction was continued for another 3 hours at 80°C to obtain an aqueous dispersion containing non-conductive organic particles.

[0104] Comparative Example 8 In preparing the slurry composition for the heat-resistant layer, 4 parts (corresponding to the solid content) of carboxymethylcellulose (manufactured by Daicel FineChem Corporation, product name "D1220") having an etherification degree of 0.8 to 1.0 was used instead of 4 parts (corresponding to the solid content) of the aqueous solution containing the water-soluble polymer. In the same manner as in Example 1, an aqueous dispersion containing non-conductive organic particles, an aqueous dispersion containing a particulate polymer, a slurry composition for the heat-resistant layer, a negative electrode, a positive electrode, a separator, and a lithium ion secondary battery were prepared or produced. Then, evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0105] Comparative Example 9 In preparing the slurry composition for the heat-resistant layer, 4 parts (corresponding to solids) of polyvinyl alcohol (manufactured by Kuraray Co., Ltd., product name "PVA110") were used instead of 4 parts (corresponding to solids) of the aqueous solution containing the water-soluble polymer, but in the same manner as in Example 1, an aqueous dispersion containing non-conductive organic particles, an aqueous dispersion containing a particulate polymer, a slurry composition for the heat-resistant layer, a negative electrode, a positive electrode, a separator, and a lithium ion secondary battery were prepared or produced. Then, evaluations were performed in the same manner as in Example 1. The results are shown in Table 2.

[0106] In addition, in Tables 1 and 2 shown below, "AAm" indicates an acrylamide unit; "DMAAm" indicates a dimethylacrylamide unit, "MAAm" indicates a methacrylamide unit; "AA" represents an acrylic acid unit; "ATBS" indicates a 2-acrylamido-2-methylpropanesulfonic acid unit; "HEAAm" indicates an N-hydroxyethylacrylamide unit; "HEMA" indicates 2-hydroxyethyl methacrylate units; "MAN" represents a methacrylonitrile unit; "EDMA" stands for ethylene glycol dimethacrylate, "BA" indicates n-butyl acrylate units; "MMA" indicates methyl methacrylate, "AGE" indicates an allyl glycidyl ether unit, "AMA" indicates an allyl methacrylate unit; "MAA" indicates a methacrylic acid unit, "AN" indicates an acrylonitrile unit, "Al 2 O 3 " indicates alumina particles, "CMC" stands for carboxymethyl cellulose; "PVA" stands for polyvinyl alcohol; ">200" indicates over 200°C.

[0107] [Table 1]

[0108] [Table 2]

[0109] From Tables 1 and 2, it can be seen that in Examples 1 to 13, which use a slurry composition for a heat-resistant layer containing a water-soluble polymer containing an amide group-containing monomer unit, an acid group-containing monomer unit, and a hydroxyl group-containing monomer unit, and in which the content ratios of the amide group-containing monomer unit and the acid group-containing monomer unit are within a predetermined range, and a non-conductive organic particle in which the content ratio of the crosslinkable monomer unit is within a predetermined range, a slurry composition for a heat-resistant layer excellent in dispersion stability and coatability and a heat-resistant layer excellent in heat shrinkage resistance and with a small amount of residual moisture can be formed. It can also be seen that the heat-resistant layers of Examples 1 to 13 can provide excellent cycle characteristics for secondary batteries. On the other hand, in Comparative Example 1, which used a slurry composition for a heat-resistant layer containing a water-soluble polymer consisting only of amide group-containing monomer units and acid group-containing monomer units, it is found that the dispersion stability and coatability of the slurry composition for a heat-resistant layer were not sufficiently ensured. In addition, in Comparative Example 2, in which a slurry composition for a heat-resistant layer containing a water-soluble polymer consisting only of amide group-containing monomer units was used, it was found that the dispersion stability and coatability of the slurry composition for a heat-resistant layer were not sufficiently ensured. Furthermore, in Comparative Example 3, which used a slurry composition for a heat-resistant layer containing a water-soluble polymer in which the content ratios of amide group-containing monomer units and acid group-containing monomer units were outside the specified ranges, it was found that the dispersion stability and coatability of the slurry composition for a heat-resistant layer were not sufficiently ensured, and a heat-resistant layer with excellent heat shrinkage resistance was not formed. In addition, in Comparative Example 4, which used a slurry composition for a heat-resistant layer containing a water-soluble polymer in which the content ratios of amide group-containing monomer units and acid group-containing monomer units were outside the specified ranges, it was found that the dispersion stability of the slurry composition for a heat-resistant layer was not sufficiently ensured, and a heat-resistant layer with excellent heat shrinkage resistance was not formed. Furthermore, in Comparative Example 5, which used a slurry composition for a heat-resistant layer containing a water-soluble polymer whose content ratio of acid group-containing monomer units was outside the specified range, it was found that the coatability of the slurry composition for a heat-resistant layer was not sufficiently ensured. In addition, in Comparative Example 6, in which a slurry composition for a heat-resistant layer not containing non-conductive organic particles was used, it is found that the amount of residual moisture in the heat-resistant layer increases and the cycle characteristics of the secondary battery decrease. In addition, in Comparative Example 7, in which a slurry composition for a heat-resistant layer containing non-conductive organic particles having a content ratio of crosslinkable monomer units outside the specified range was used, a heat-resistant layer having excellent heat shrinkage resistance could not be formed, and the cycle characteristics of the secondary battery were deteriorated. Furthermore, in Comparative Examples 8 and 9, which do not contain a specific water-soluble polymer, it is found that the amount of residual moisture in the heat-resistant layer increases and the cycle characteristics of the secondary battery deteriorate. [Industrial Applicability]

[0110] According to the present invention, it is possible to provide a slurry composition for a heat-resistant layer of a non-aqueous secondary battery, which is capable of forming a heat-resistant layer for a non-aqueous secondary battery that has excellent dispersion stability and coatability, and also has excellent heat shrinkage resistance and a reduced amount of residual moisture. Furthermore, according to the present invention, it is possible to provide a heat-resistant layer for a nonaqueous secondary battery which has excellent heat shrinkage resistance and a reduced amount of residual moisture, and a nonaqueous secondary battery including the heat-resistant layer.

Claims

1. A slurry composition for a non-aqueous secondary battery heat-resistant layer, comprising a water-soluble polymer, non-conductive organic particles, and water, the water-soluble polymer comprises an amide group-containing monomer unit, an acid group-containing monomer unit, and a hydroxyl group-containing monomer unit; the water-soluble polymer has an amide group-containing monomer unit content of 63% by mass or more and 98% by mass or less and an acid group-containing monomer unit content of 1% by mass or more and 20% by mass or less, The non-conductive organic particles include crosslinkable monomer units, The content ratio of the crosslinkable monomer unit in the non-conductive organic particles is 20% by mass or more and 95% by mass or less, The non-conductive organic particles have a glass transition temperature of 200° C. or higher; A slurry composition for a nonaqueous secondary battery heat-resistant layer, wherein the content of the water-soluble polymer is 0.5 parts by mass or more and 20 parts by mass or less per 100 parts by mass of the non-conductive organic particles.

2. The slurry composition for a nonaqueous secondary battery heat-resistant layer according to claim 1 , wherein the content of the hydroxyl group-containing monomer unit in the water-soluble polymer is from 1% by mass to 25% by mass.

3. 3. The slurry composition for a non-aqueous secondary battery heat-resistant layer according to claim 1, wherein the hydroxyl group-containing monomer unit is a hydroxyl group-containing (meth)acrylamide monomer unit.

4. The slurry composition for a non-aqueous secondary battery heat-resistant layer according to any one of claims 1 to 3, wherein the molar ratio of the content of the hydroxyl group-containing monomer unit to the content of the acid group-containing monomer unit in the water-soluble polymer is 0.70 or more.

5. Further comprising a particulate polymer, 5. The slurry composition for a non-aqueous secondary battery heat-resistant layer according to claim 1, wherein the particulate polymer has a glass transition temperature of less than 20°C.

6. A heat-resistant layer for a non-aqueous secondary battery, formed using the slurry composition for a heat-resistant layer for a non-aqueous secondary battery according to any one of claims 1 to 5.

7. A non-aqueous secondary battery comprising the heat-resistant layer for a non-aqueous secondary battery according to claim 6 .

Citation Information

Patent Citations

  • Slurry for secondary battery porous film, porous film for secondary battery, manufacturing method thereof, and application

    JP2014203680A

  • Lithium ion secondary battery separator, method for manufacturing lithium ion secondary battery separator, and lithium ion secondary battery

    JP2018026266A

  • Binder aqueous solution for lithium ion battery, slurry for lithium ion battery, manufacturing methods thereof, electrode for lithium ion battery, separator for lithium ion battery, separator / electrode laminate for lithium ion battery, and lithium ion battery

    JP2019057487A

  • Slurry for thermal crosslinking type lithium ion battery, manufacturing method thereof, electrode for lithium ion battery, separator for lithium ion battery, separator / electrode laminate for lithium ion battery, and lithium ion battery

    JP2019057488A

  • Separator for secondary battery, method for manufacturing the same, and lithium secondary battery including the same

    JP2019075374A